Optical film and image display device
Patent Information
- Application Number
- CN202580023835.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2025-03-28
- Publication Date
- 2026-10-30
AI Technical Summary
因此,由于作为基材的聚酯薄膜与硬涂层的折射率差,有可能产生呈彩虹状不均的干涉条纹
[0055]根据本发明的一个方式,能够提供不易产生干涉条纹的可折叠的光学薄膜。另外,根据本发明的另一个方式,能够提供具备这种光学薄膜的图像显示装置。
Smart Images

Figure CN123022548A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to optical thin films and image display devices. Background Technology
[0002] Previously, image display devices such as smartphones and tablets were known, but foldable image display devices are currently under development. Typically, smartphones and tablets are covered with protective glass. While glass is generally very hard, it is inflexible. Therefore, if a protective glass is used in an image display device, the likelihood of breakage is high if it is folded. Therefore, the use of a foldable optical film to replace the protective glass in a foldable image display device has been investigated. This optical film has a hard coating and a polyester film as a flexible substrate (see, for example, Patent Document 1).
[0003] In such foldable optical films, the resin constituting the polyester film, which is typically a flexible substrate, has a high refractive index, thus increasing the refractive index difference between the polyester film and the hard coating. Consequently, due to the refractive index difference between the polyester film and the hard coating, it is possible to generate rainbow-like, uneven interference fringes.
[0004] To suppress the generation of interference fringes, there are methods to increase the thickness of the hard coating. However, if the thickness of the hard coating is increased, there is a problem that the hard coating will crack when folded. Therefore, at present, an optical thin film that can be folded and is not prone to generating interference fringes has not yet been obtained.
[0005] Existing technical documents
[0006] Patent documents
[0007] Patent Document 1: Japanese Patent Application Publication No. 2016-125063 Summary of the Invention
[0008] The problem the invention aims to solve
[0009] This invention was made in light of the aforementioned problems in the prior art. Specifically, the object of this invention is to provide a foldable optical thin film that is less prone to generating interference fringes, and an image display device incorporating this optical thin film.
[0010] Solution for solving the problem
[0011] To achieve the above objectives, the inventors conducted in-depth research, resulting in the completion of this invention. Specifically, this invention comprises the following technical solutions. [1]
[0013] An optical thin film, which is a foldable optical thin film for an image display device, has the following characteristics:
[0014] Polyester film as substrate,
[0015] Functional layer disposed on the first side of the substrate
[0016] Resin layer A disposed between the substrate and the functional layer, and
[0017] Resin layer B is disposed on the second side of the substrate, which is opposite to the first side.
[0018] The thickness of resin layer A is greater than 10 nm and less than 500 nm.
[0019] The thickness of the resin layer B is greater than 1 nm and less than 200 nm.
[0020] When repeatedly folded 180° 10,000 times with the functional layer as the inside and the opposite edges of the optical film spaced 10 mm apart, no cracks or breaks occur in the optical film. [2]
[0022] According to the optical thin film described in [1], the refractive index of the resin layer A is lower than that of the substrate and higher than that of the functional layer. [3]
[0024] According to the optical film described in [1] or [2], the resin layer C is disposed between the substrate and the resin layer A. [4]
[0026] According to the optical thin film described in [3], the thickness of the resin layer C is 30 nm or more and 200 nm or less. [5]
[0028] The optical thin film according to any one of [1] to [4], wherein,
[0029] An adhesive layer is also provided on the second side of the polyester film, which is the opposite side to the first side, which serves as the substrate.
[0030] The adhesive layer has a film thickness of 25 μm or more and 300 μm or less.
[0031] The shear storage modulus G' of the optical thin film in the frequency region above 500Hz and below 1000Hz at 25℃ exceeds 200MPa and is below 1200MPa.
[0032] The shear loss modulus G” of the optical thin film in the frequency region of 25°C and above 500Hz and below 1000Hz is above 3MPa and below 150MPa. [6]
[0034] The optical film according to any one of [1] to [5], wherein the resin layer B is disposed between the substrate and the adhesive layer. [7]
[0036] The optical film according to any one of [1] to [6], wherein the yellow index of the optical film is 15 or less. [8]
[0038] According to any one of [1] to [7], the optical film does not crack or break when repeatedly folded 180° with the functional layer on the outside and the opposite edges of the optical film spaced 30 mm apart, for 10,000 cycles. [9]
[0040] The optical film according to any one of [1] to [8], wherein the resin layer A is a cured layer of a curable resin composition formed from a composition comprising a polycarbonate polyurethane resin (A-1), a polyester resin (A-2), a capped isocyanate crosslinking agent (A-3) and particles (A-4), wherein the polyester resin (A-2) has a fused polycyclic aromatic structure.
[10]
[0042] The optical film according to any one of [1] to [9], wherein the resin layer B is a cured layer of a curable resin composition formed from a composition comprising a polycarbonate polyurethane resin (B-1), a polyester resin (B-2), a capped isocyanate crosslinking agent (B-3) and particles (B-4), wherein the polyester resin (B-2) has a fused polycyclic aromatic structure.
[11]
[0044] The optical film according to any one of [3] to
[10] , wherein the resin layer C is a cured layer of a curable resin composition formed from a composition comprising a polycarbonate polyurethane resin (C-1), a polyester resin (C-2), a capped isocyanate crosslinking agent (C-3) and particles (C-4), wherein the polyester resin (C-2) has a fused polycyclic aromatic structure.
[12]
[0046] The optical film according to [9],
[10] or
[11] , wherein at least one of the polyester resins (A-2), (B-2) and (C-2) having a fused polycyclic aromatic structure contained in the resin layer A, resin layer B and resin layer C has a naphthalene skeleton in its molecule.
[13]
[0048] A method for manufacturing an optical thin film, which is the method for manufacturing an optical thin film as described in any one of [1] to
[12] , comprising:
[0049] A functional layer is manufactured on the first side of the polyester film, which serves as the substrate, through a coating process.
[14]
[0051] A foldable image display device comprising a display element and an optical film as described in any one of [1] to
[12] disposed closer to the observer than the display element.
[15]
[0053] According to the image display device described in
[14] , the display element is an organic light-emitting diode element.
[0054] The effects of the invention
[0055] According to one aspect of the present invention, a foldable optical thin film that is not prone to generating interference fringes can be provided. Furthermore, according to another aspect of the present invention, an image display device incorporating such an optical thin film can be provided. Attached Figure Description
[0056] Figure 1 This is a simplified structural diagram of an optical thin film according to one embodiment.
[0057] Figure 2 This is a schematic diagram illustrating the folding test.
[0058] Figure 3 This is a schematic diagram showing the state of the optical film after another type of folding test.
[0059] Figure 4 This is a simplified structural diagram of an optical thin film according to one embodiment.
[0060] Figure 5 This is a simplified structural diagram of an optical thin film according to one embodiment. Detailed Implementation
[0061] The optical thin film and image display device of the present invention will now be described with reference to the accompanying drawings. In this specification, the terms "thin film," "sheet," etc., are not distinguished from each other merely based on different names. Therefore, for example, "thin film" is used to also include components that are also called sheets. Figure 1 This is a simplified structural diagram of an optical thin film according to one embodiment. Figure 2 (A) and Figure 2 (B) is a schematic diagram illustrating the folding test. Figure 3 This is a schematic diagram showing the state of the optical thin film after the folding test.
[0062] (Optical thin film)
[0063] Figure 1The optical thin film 10 shown is used in an image display device and is foldable.
[0064] The optical film 10 includes: a polyester film 11 as a substrate; a functional layer 12 disposed on one side of the polyester film 11 as a substrate, namely the first side 11A; and a resin layer A13 disposed between the polyester film 11 as a substrate and the functional layer 12, and the optical film 10 has a resin layer B15 disposed on a second side 11B of the substrate opposite to the first side 11A.
[0065] In another embodiment, a resin layer C14 may be further provided between the polyester film 11 serving as the substrate and the resin layer A (e.g., see reference). Figure 4 ).
[0066] Optical thin film 10 can also be an optical thin film as described later. Figure 4 In this way, an adhesive layer 41 is also provided on the second side 11B of the polyester film 11, which serves as the substrate.
[0067] In this specification, "functional layer" refers to a layer in an optical thin film intended to perform a certain function. Specifically, examples of functional layers include hard coatings, antistatic layers, and antifouling layers. Functional layer 12 is preferably a hard coating. Furthermore, while functional layer 12 is a single-layer structure, it can also be a multi-layer structure with two or more layers (e.g., 2-layer, 3-layer, 4-layer, etc.). Similarly, each resin layer in this specification can be a single-layer structure or a multi-layer structure with two or more layers (e.g., 2-layer, 3-layer, 4-layer, etc.). A single-layer structure is preferred. For example, the resin layers can be formed through a multi-stage coating process, or a multi-layer structure can be used so that particles exist near the surface of each resin layer.
[0068] In one embodiment, other resin layers may be further disposed between resin layer A13 and functional layer 12.
[0069] The optical film 10 is foldable. Specifically, it does not crack or break when repeatedly folded 180° with the functional layer 12 inside and the opposite edges of the optical film 10 spaced 10 mm apart, even after 10,000 folding tests. Preferably, the optical film 10 does not crack or break even after 20,000 folding tests, and even more preferably, it does not crack or break even after 100,000 folding tests.
[0070] If the optical film 10 is cracked or otherwise damaged during repeated 10,000 folding tests, then the foldability of the optical film 10 is insufficient.
[0071] On the other hand, it is preferable that even when the optical film 10 is repeatedly folded 10,000 times in a manner with the functional layer 12 on the outside and the opposite edges of the optical film 10 spaced 30 mm apart (also known as a continuous folding test), the optical film 10 does not crack or break. More preferably, even when the continuous folding test is repeated 20,000 times, the optical film 10 does not crack or break. Even more preferably, even when repeated 100,000 times, the optical film 10 does not crack or break.
[0072] Here, when bending the optical film 10 with the functional layer 12 on the outside, compared to a folding test with the functional layer on the inside, since stress extending along the length direction is applied to the functional layer 12, it is desirable to conduct a test of continuously folding the optical film 10 with a spacing of 30 mm between the opposite edges of the optical film 10. This is based on the insight that the functional layer is less resistant to elongation stress applied by tension than to contraction stress applied by compression. For example, when bending with the functional layer on the outside, the elongation stress applied to the functional layer increases, thus making it suitable to use test conditions that change the folding interval.
[0073] Therefore, the evaluation method can be different when the functional layer 12 is bent inside and when the functional layer 12 is bent outside.
[0074] By having at least one of the resin layers A to C have the composition described in this specification, the present invention can yield good results even in evaluations of bending with the functional layer 12 on the outside.
[0075] The continuous folding test of the optical thin film 10, with the functional layer 12 as the inner side, was conducted as follows. For example... Figure 2 As shown in (A), in the continuous folding test, the optical film 10 is first fixed to the parallel-arranged fixing part 20 with its edges facing each other. It should be noted that the optical film 10 can be of any shape, but the optical film 10 in the continuous folding test is preferably rectangular (e.g., a rectangle of 30mm × 100mm). For example, as... Figure 2 As shown in (A), a structure in which one fixing part 20 is fixed to the platform and the other fixing part slides up and down can also be adopted.
[0076] Next, as Figure 2As shown in (B), by moving the fixing part 20 in a way that brings them closer together, the optical film 10 is deformed in such a way that the functional layer 12 becomes the inside and the optical film 10 is folded. Then, after moving the fixing part 20 to a position where the distance between the two opposite sides of the optical film 10 fixed by the fixing part 20 is 10 mm, the fixing part 20 is moved in the opposite direction to eliminate the deformation of the optical film 10.
[0077] After this process, the optical film is repeatedly folded 180° 10,000 times with the functional layer as the inner side and the opposite edges of the optical film spaced 10 mm apart. The optical film of the present invention does not crack or break after repeated 10,000 folding tests.
[0078] In this invention, preventing the optical film from cracking or breaking means investigating whether a lift (gap) occurs between the substrate and the functional layer, and also investigating whether cracking or breaking occurs at the bend. Cracks or breaks can be evaluated visually.
[0079] like Figure 2 As shown in (A), the optical film 10 can be folded 180° by moving the fixing part 20. Furthermore, by performing a continuous folding test in a manner where the curved portion of the optical film 10 does not protrude from the end of the fixing part 20, and by controlling the interval between the fixing parts 20 when they are closest to each other to be 10 mm, the interval between the two opposite edges of the optical film 10 can be set to 10 mm. In this case, the outer diameter of the curved portion is replaced with 10 mm.
[0080] The thickness of the optical film 10 is sufficiently small compared to the spacing (10 mm) of the fixing portion 20. Therefore, it is assumed that the results of the continuous folding test of the optical film 10 are not affected by the difference in the thickness of the optical film 10. In this invention, when a continuous folding test is repeatedly performed 10,000 times with the functional layer 12 as the inner side and the spacing between the opposite edges of the optical film 10 being 10 mm apart, no cracking or breakage occurs in the optical film 10. Even when a continuous folding test is repeatedly performed 10,000 times with the functional layer 12 as the inner side and the spacing between the opposite edges of the optical film 10 being 2 mm apart, no cracking or breakage occurs in the optical film 10.
[0081] Preferably, by having at least one of layers A to C have the composition described in this specification, good results can be shown in these successive tests.
[0082] As another evaluation of folding, the optical film 10 was fixed to the fixing part 20 with a 10mm gap between one end and the other opposite end. With the optical film 10 folded, it was held at 70°C for 12 hours (a folding retention test was performed). Figure 3 As shown, after the folding retention test, the folded state was released, and after 30 minutes at room temperature, the opening angle, i.e., the opening angle θ, of the optical film 10 was measured.
[0083] In this evaluation test, the opening angle θ of the optical thin film 10 is preferably 100° or greater. It should be noted that a larger opening angle θ means better resilience, with a maximum of 180°. The folding retention test can be performed by folding the optical thin film 10 with the functional layer 12 as the inner side, or by folding the optical thin film 10 with the functional layer 12 as the outer side, but in either case, an opening angle θ of 100° or greater is preferred.
[0084] The hardness (pencil hardness) of the surface of the optical thin film 10 (the surface of the functional layer 12) measured according to the pencil hardness test specified in JIS K5600-5-4:1999 is preferably 3H or higher, more preferably 4H or higher. The pencil hardness test is performed as follows: An optical thin film 10 cut to a size of 30mm × 100mm is fixed to a glass plate without bending or wrinkling using a Cellotte (registered trademark) manufactured by NICHIBAN Co., Ltd. The test is conducted on the surface of the optical thin film using a pencil hardness testing machine (product name "Pencil Scratch Coating Hardness Tester (Electric Type)", manufactured by Toyo Seiki Co., Ltd.) while applying a load of 750g to a pencil (product name "Uni", manufactured by Mitsubishi Pencil Co., Ltd.) and moving the pencil at a moving speed of 1mm / second. The pencil hardness is set as the highest hardness that does not cause damage to the surface of the optical thin film during the pencil hardness test. It should be noted that multiple pencils of different hardness are used to determine the pencil hardness. However, each pencil undergoes five pencil hardness tests. If the pencil does not cause damage to the surface of the optical film in four or more of the five tests, it is considered that the pencil of that hardness has not caused damage to the surface of the optical film. The aforementioned damage refers to visually identifiable damage by transmitting light through the optical film surface after the pencil hardness test under fluorescent light.
[0085] The optical film 10 preferably has a yellow index (YI) of 15 or less. If the YI of the optical film 10 is 15 or less, the yellow tint of the optical film can be suppressed, and it can be used in applications requiring transparency. The upper limit of the yellow index (YI) of the optical film 10 is more preferably 10 or less. The yellow index (YI) is calculated as follows: the measurement is performed with an optical film cut to a size of 50mm × 50mm arranged in a spectrophotometer (product name "UV-2450", manufactured by Shimadzu Corporation, light source: tungsten lamp and deuterium lamp) with the back side as the light source side, the tristimulus values X, Y, and Z of the optical film are calculated according to the formula described in JIS Z8722:2009 based on the measured transmittance of the optical film at wavelengths of 300nm to 780nm, and the values are calculated according to the formula described in ASTM D1925:1962 based on the tristimulus values X, Y, and Z. The upper limit of the yellow index (YI) of the optical film 10 is preferably 10 or less. The aforementioned yellow index (YI) is the arithmetic mean of the values obtained from three measurements of one optical film. It should be noted that in the UV-2450, the aforementioned transmittance measurement data is read on a monitor connected to the UV-2450, and the item "YI" is selected in the calculation items to calculate the yellow index. The transmittance at wavelengths from 300 nm to 780 nm is determined by measuring the transmittance at the lowest five points within 1 nm intervals between wavelengths from 300 nm to 780 nm under the following conditions, and calculating their average value. Furthermore, if fluctuations occur in the spectral transmittance, smoothing can be performed with a Δ5.0 nm.
[0086] (Measurement conditions)
[0087] Wavelength range: 300nm~780nm
[0088] • Scanning speed: High speed
[0089] • Slit width: 2.0
[0090] • Sampling interval: Automatic (0.5nm interval)
[0091] Lighting: C
[0092] • Light source: D2 and WI
[0093] • Field of view: 2°
[0094] • Light source switching wavelength: 360nm
[0095] • S / R switching: Standard
[0096] • Detector: PM
[0097] • Automatic zeroing: Performed at 550nm after baseline scan
[0098] To adjust the yellow index (YI) of the optical thin film 10, for example, in Figure 1 In the structure shown, at least any one of the polyester film 11, functional layer 12, resin layer A13, and resin layer B15, which serve as the substrate, may contain a blue pigment that is the complementary color to yellow. In another embodiment, when resin layer C is present, resin layer C may also contain a blue pigment that is the complementary color to yellow.
[0099] The aforementioned blue pigment can be any of pigments or dyes. For example, when the optical film 10 is used in an organic light-emitting diode display device, a pigment that combines lightfastness and heat resistance is preferred. Compared to dyes with molecular dispersion, polycyclic organic pigments and metal complex organic pigments exhibit less molecular breakage due to ultraviolet light and thus have particularly excellent lightfastness. Therefore, they are preferred for applications requiring lightfastness, and more specifically, phthalocyanine-based organic pigments are suitable examples. However, since pigments are partically dispersed in the solvent, there is a barrier to transparency caused by particle scattering. Therefore, it is preferable to ensure that the particle size of the pigment dispersion falls within the Rayleigh scattering region. On the other hand, when the transparency of the optical film is important, dyes that are molecularly dispersed in the solvent are preferred as the aforementioned blue pigment. Additionally, inorganic pigments such as cobalt blue can also be used as the aforementioned blue pigment.
[0100] Light with a continuous spectrum in the region of wavelength above 300 nm and below 780 nm is irradiated onto the optical thin film 10 from the resin layer B15 side at an incident angle of 0°. The L of the light transmitted through the optical thin film 10 (transmitted light) is calculated. * a * b * The color coordinates a of the color system * b * When, a is preferred * For values between -3.0 and 2.0, b * It is above -2.0 and below 8.0. If a * and b * Within the aforementioned ranges, the yellow index can be kept below 15. * and b * The determination can be performed using a spectrophotometer (product name "UV-2450", manufactured by Shimadzu Corporation). As a light source, examples include using a tungsten halide (WI) lamp alone or in combination with a deuterium (D2) lamp and a tungsten halide (WI) lamp. In this specification, "light with an incident angle of 0°" refers to light in the normal direction when the normal direction of the first surface of the optical thin film is set to 0°. "L" * a * b * Color system", a* " and "b * According to JIS Z8729:2004.
[0101] The spectral transmittance of the optical film 10 at a wavelength of 380 nm is preferably 8% or less. If the spectral transmittance of the optical film exceeds 8%, the polarizer may be exposed to ultraviolet light and degrade easily when the optical film is used in a mobile terminal. The transmittance can be measured using a spectrophotometer (product name "UV-2450", manufactured by Shimadzu Corporation). The measurement conditions for the spectral transmittance are the same as those for the spectral transmittance at wavelengths of 300 nm to 780 nm. The transmittance is measured three times for an optical film cut to a size of 50 mm × 100 mm, and the arithmetic mean of the three measurements is taken. The upper limit of the transmittance of the optical film 10 is more preferably 5%. It should be noted that the transmittance of the optical film 10 can be achieved by adjusting the amount of ultraviolet absorber added, as described later.
[0102] The total light transmittance of the optical film 10 is preferably 85% or higher. If the total light transmittance of the optical film 10 is 85% or higher, sufficient image visual recognition can be obtained when the optical film 10 is used in a mobile terminal. More preferably, the total light transmittance of the optical film 10 is 87% or higher, and most preferably, it is 90% or higher.
[0103] The aforementioned total transmittance can be measured using a haze meter (product name "HM-150", manufactured by Murakami Color Technology Research Institute Co., Ltd.) according to the method of JIS K7361-1:1997. The aforementioned total transmittance is as follows: after cutting the optical film into pieces of 50mm × 100mm, and setting it in a state free from curling, wrinkles, fingerprints, dust, etc., the transmittance is measured three times for each piece of optical film, and the arithmetic mean of the three measurements is taken. In this specification, "measured three times" does not refer to measuring three times at the same location, but rather to measuring three different locations. In the optical film 10, the visually inspected surface 10A is flat, and the layers to be stacked, such as the functional layer 12, are also flat; furthermore, the film thickness deviation falls within ±10%. Therefore, it is believed that by measuring the total transmittance at three different locations on the cut optical film, an approximate average of the total transmittance of the entire in-plane optical film can be obtained. Regardless of whether the measured object is a 1m × 3000m strip or the size of a 5-inch smartphone, the deviation in total transmittance is within ±10%. It should be noted that in cases where the optical film cannot be cut to the aforementioned size, for example, the HM-150 has an entrance opening of 20mmφ during measurement, thus requiring a sample size with a diameter of 21mm or more, the optical film can be appropriately cut to a size of 22mm × 22mm or more. When the optical film size is small, the measurement points can be adjusted by gradually shifting or changing the angle within a range where the light source spot does not deviate, resulting in three measurement locations.
[0104] The haze value (total haze value) of the optical film 10 is preferably 2.5% or less. If the haze value of the optical film is 2.5% or less, whitening of the image display surface can be suppressed when the optical film is used in a mobile terminal. The haze value is more preferably 1.5% or less, and more preferably 1.0% or less.
[0105] The aforementioned haze value can be measured using a haze meter (product name "HM-150", manufactured by Murakami Color Technology Research Institute Co., Ltd.) according to the method of JIS K7136:2000. The haze value is as follows: after cutting the optical film into 50mm × 100mm pieces, and setting it in a state free of curling, wrinkles, fingerprints, dust, etc., the measurement is taken three times for each optical film, and the arithmetic mean of the three measurements is taken. In the optical film 10, the visually visible surface 10A is flat, and the layers to be stacked, such as the functional layer 12, are also flat. Furthermore, the film thickness deviation falls within ±10%. Therefore, it is believed that by measuring the haze value at three different locations on the cut optical film, an approximate average of the overall in-plane haze value of the optical film can be obtained. Regardless of whether the measured object is a 1m × 3000m strip or the size of a 5-inch smartphone, the deviation of the haze value is within ±10%. It should be noted that in cases where the optical film cannot be cut to the aforementioned size, for example, the HM-150 has an entrance opening of 20mmφ during measurement, thus requiring a sample size with a diameter of 21mm or more, the optical film can be appropriately cut to a size of 22mm × 22mm or more. When the size of the optical film is small, the measurement points can be determined by gradually shifting or changing the angle within a range where the light source spot does not deviate, resulting in three measurement locations.
[0106] When a polarizing plate or other films are provided on the first side of the optical film 10 via an adhesive layer or bonding layer, after peeling the other films together with the adhesive layer or bonding layer, folding tests, fold retention tests, yellow index measurements, total transmittance measurements, and haze value measurements are performed. The peeling of the other films can be performed, for example, as follows: First, for a laminate with other films attached to the optical film via an adhesive layer or bonding layer, a desiccant is used to heat the laminate, and the tip of a scalpel is inserted into the area considered the interface between the optical film and the other films, and peeling is performed slowly. By repeatedly performing this heating and peeling, the adhesive layer, bonding layer, and other films can be peeled off. It should be noted that even with this peeling process, there is no significant impact on these tests and measurements. The haze value measurement is performed after the adhesive layer or bonding layer is peeled off, and the stains on the adhesive layer or bonding layer are further wiped clean with alcohol.
[0107] In recent years, light-emitting diodes (LEDs) have been widely used as backlight sources for image display devices such as personal computers and tablets. However, these LEDs emit strong blue light. This blue light, with a wavelength of 380nm to 495nm, has properties close to ultraviolet light and possesses high energy. Therefore, it is not absorbed by the cornea or lens and reaches the retina, potentially causing retinal damage, eye fatigue, and adverse effects on sleep. Therefore, when applying optical films to image display devices, it is preferable to have excellent blue light blocking properties without affecting the color tone of the displayed image. Thus, from the viewpoint of blocking blue light, the optical film 10 preferably has a spectral transmittance of less than 1% at a wavelength of 380nm, less than 10% at a wavelength of 410nm, and more than 70% at a wavelength of 440nm. This is because if the spectral transmittance at wavelength 380nm is 1% or more, or the spectral transmittance at wavelength 410nm is 10% or more, problems caused by blue light may not be eliminated. If the spectral transmittance at wavelength 440nm is less than 70%, it may sometimes affect the color tone of the image displayed in an image display device using an optical thin film. The optical thin film 10 can sufficiently absorb light in the wavelength region below 410nm of blue light, while allowing sufficient transmission of light above 440nm, thus providing excellent blue light shielding without affecting the color tone of the displayed image. Furthermore, when such an optical thin film 10 with excellent blue light shielding is applied to an organic light-emitting diode (OLED) display device, it is also effective in suppressing the degradation of the OLED element.
[0108] The transmittance of the optical thin film 10 is preferably almost 0% before wavelength 380 nm, gradually increasing from wavelength 410 nm, and sharply increasing near wavelength 440 nm. Specifically, for example, it is preferable that the spectral transmittance changes in an S-shaped curve between wavelengths 410 nm and 440 nm. The aforementioned spectral transmittance at wavelength 380 nm is more preferably less than 0.5%, even more preferably less than 0.2%, the spectral transmittance at wavelength 410 nm is more preferably less than 7%, even more preferably less than 5%, and the spectral transmittance at wavelength 440 nm is more preferably 75% or more, even more preferably 80% or more. It should be noted that the spectral transmittance of the optical thin film 10 is preferably less than 50% at wavelength 420 nm. By satisfying this spectral transmittance relationship, the transmittance of the optical thin film 10 increases sharply near wavelength 440 nm, achieving extremely excellent blue light blocking performance without affecting the color tone of the displayed image.
[0109] The spectral transmittance of the optical thin film 10 at a wavelength of 380 nm is more preferably less than 0.1%, the spectral transmittance at a wavelength of 410 nm is more preferably less than 7%, and the spectral transmittance at a wavelength of 440 nm is more preferably 80% or more.
[0110] The optical thin film 10 preferably has a transmittance spectrum with a slope greater than 2.0 in the wavelength range of 415-435 nm obtained using the least squares method. When the slope is less than 2.0, light may not be sufficiently intercepted in the blue light wavelength region, such as the wavelength range of 415-435 nm, resulting in a weaker blue light interception effect. Furthermore, considering the possibility of excessive interception in the blue light wavelength region (415-435 nm), interference with the backlight and emission wavelength region of the image display device (e.g., emission from an OLED at a wavelength of 430 nm) is possible, increasing the likelihood of adverse effects such as color distortion. This slope can be calculated, for example, using a spectrophotometer (product name "UV-2450", manufactured by Shimadzu Corporation) capable of measurement in 0.5 nm scales, by measuring transmittance data at a minimum of five points within the 415-435 nm range, 1 nm before and after.
[0111] The optical thin film 10 preferably has a blue light blocking rate of 40% or more. When the blue light blocking rate is less than 40%, it is sometimes impossible to sufficiently eliminate the problems caused by the aforementioned blue light. The aforementioned blue light blocking rate is, for example, a value calculated according to JIS T7333:2005. It should be noted that such a blue light blocking rate can be achieved, for example, by including the sesamol-type benzotriazole monomer described later in the functional layer 12.
[0112] The application of the optical film 10 is not particularly limited. Examples of applications for the optical film 10 include image display devices such as smartphones, tablets, personal computers (PCs), wearable devices, digital signage, televisions, and car navigation systems. Furthermore, the optical film 10 is also suitable for automotive applications. As for the form of the aforementioned image display devices, foldable or rollable designs are preferred for applications requiring flexibility.
[0113] The optical film 10 can be cut to the desired size or rolled up. When the optical film 10 is cut to the desired size, its size is not particularly limited and is appropriately determined based on the size of the display surface of the image display device. Specifically, the size of the optical film 10 can be, for example, 2.8 inches or more and 500 inches or less. Regarding the term "inch" in this specification, when the optical film is quadrilateral, it refers to the length of the diagonal; when it is circular, it refers to the diameter; and when it is elliptical, it refers to the average of the sum of the minor and major axes. Here, when the optical film is quadrilateral, the aspect ratio of the optical film when calculating the aforementioned inches is not particularly limited, as long as it does not cause problems with the display screen of the image display device. For example, aspect ratios such as 1:1, 4:3, 16:10, 16:9, and 2:1 can be given. However, such aspect ratios are not limited, especially in design-oriented automotive applications and digital signage. In addition, if the optical film 10 is large, it can be cut into A5 size (148mm×210mm) from any position and then cut into the size of each measurement item.
[0114] The optical thin film 10 in the image display device can be disposed inside the image display device, but is preferably near the surface of the image display device. When disposed near the surface of the image display device, the optical thin film 10 functions as a protective film used instead of protective glass.
[0115] (Polyester film as substrate)
[0116] The polyester film 11, serving as the substrate, is translucent. In this specification, "translucent" refers to the property of allowing light to pass through, including, for example, a total transmittance of 50% or more, preferably 70% or more, more preferably 80% or more, and particularly preferably 90% or more. Translucentness does not necessarily mean transparency; it can also be translucent.
[0117] The polyester film 11, which serves as the substrate, is a substrate made of polyester resin (e.g., polyethylene terephthalate resin, polyethylene naphthalate resin).
[0118] The polyester film is not only resistant to cracking or breaking during continuous folding tests, but also has excellent hardness and transparency, and excellent adhesion to the resin layer of this invention.
[0119] There are no particular limitations on the materials of polyester resins; copolymers formed by the condensation of dicarboxylic acid components and diol components, or their blends, can be used.
[0120] Examples of dicarboxylic acid components that constitute polyester resins include terephthalic acid, isophthalic acid, phthalic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, diphenylcarboxylic acid, diphenoxyethanedicarboxylic acid, diphenylsulfonecarboxylic acid, anthracene dicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, hexahydroterephthalic acid, hexahydroisophthalic acid, malonic acid, dimethylmalonic acid, succinic acid, 3,3-diethylsuccinic acid, glutaric acid, 2,2-dimethylglutaric acid, adipic acid, 2-methyl adipic acid, trimethyl adipic acid, pimelic acid, azelaic acid, dimer acid, sebacic acid, octanoic acid, and dodecanedicarboxylic acid.
[0121] Examples of diols that constitute polyester resins include ethylene glycol, propylene glycol, hexamethylene glycol, neopentyl glycol, 1,2-cyclohexanediethanol, 1,4-cyclohexanediethanol, decamethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 2,2-bis(4-hydroxyphenyl)propane, and bis(4-hydroxyphenyl)sulfone.
[0122] One or more dicarboxylic acid components and two diol components can be used. In addition, other polycarboxylic acid components such as trimellitic acid and other polyol components such as trimethylolpropane can also be added appropriately.
[0123] Specifically, examples of polyester resins include polyethylene terephthalate, polyethylene terephthalate, polyethylene terephthalate, and polyethylene naphthalate. Among these, polyethylene terephthalate is preferred from the perspective of balancing physical properties and cost. Furthermore, including other copolymer components and other polymers is also a preferred approach to control optical properties such as polarization. From the viewpoint of controlling the optical properties of polyester films, preferred copolymer components include diethylene glycol and copolymer components with norbornene side chains.
[0124] The intrinsic viscosity of the polyester resin (solvent: phenol / tetrachloroethane = 60:40) is, for example, 0.50~1.0 dl / g.
[0125] The polyester film is a film mainly composed of the aforementioned polyester resin. Here, "film mainly composed of polyester resin" refers to a film formed from a resin composition containing 50% by mass or more of polyester resin. When blended with other polymers (e.g., polycarbonate resin, polyimide resin, etc.), it means containing 50% by mass or more of polyester resin; when copolymerized with other monomers, it means containing 50% by mole or more of polyester structural units. Preferably, the polyester film contains 90% by mass or more, more preferably 95% by mass or more, and even more preferably 100% by mass of polyester resin.
[0126] To improve the handling properties of polyester films, such as their slip properties and winding properties, the films can contain inactive particles. Examples of inactive particles include inorganic particles such as silica, kaolinite, talc, light calcium carbonate, heavy calcium carbonate, zeolite, alumina, barium sulfate, carbon black, zinc oxide, zinc sulfate, zinc carbonate, titanium dioxide, satin white, aluminum silicate, diatomaceous earth, calcium silicate, aluminum hydroxide, hydrated halloysite, magnesium carbonate, and magnesium hydroxide. The average particle size of these inactive particles can be, for example, 200–5000 nm, or even 250–4500 nm. This average particle size is determined using the method described in the examples (average particle size based on the number of particles measured by SEM).
[0127] To maintain high transparency, it is preferable that the content of inactive particles in the film is as low as possible. Therefore, it is preferable to form a multilayer structure in which particles are present only on the surface of the film, or to have no particles in the film at all, with particles present only in the resin layer on at least one side of the polyester film.
[0128] It should be noted that "substantially free of particles" means, for example, in the case of inorganic particles, that when quantitative analysis of elements derived from particles is performed by fluorescence X-ray analysis, the content is less than 50 ppm, preferably less than 10 ppm, and most preferably below the detection limit. This is because, even without actively adding particles to the substrate film, contaminants from foreign matter, raw material resins, or dirt adhering to the production line or equipment during the film manufacturing process can inevitably be mixed into the film.
[0129] Furthermore, when the polyester film is made into a multilayer structure, two three-layer structures can be produced, in which the inner layers substantially do not contain inactive particles, and only the outermost two layers contain inactive particles. This allows for a balance between transparency and processability, and is therefore preferred.
[0130] The polyester film serving as the substrate can be a single layer or composed of two or more layers. Furthermore, various additives can be included in the film as needed, provided they are within the scope of achieving the effects of this invention. Examples of additives include antioxidants, lightfastness agents, anti-gelling agents, organic wetting agents, antistatic agents, ultraviolet absorbers, and surfactants. When the film has a laminated structure, it is also preferable to include additives as needed and according to the function of each layer. For example, adding ultraviolet absorbers to the inner layers to prevent light degradation of the polarizer is also a preferred approach.
[0131] Polyester film can be manufactured using conventional methods. For example, it can be obtained by melting and extruding a material containing the aforementioned polyester resin into a film shape and then cooling and solidifying it using a casting drum. As the polyester film of the present invention, any type of unstretched film or stretched film can be used, but stretched film is preferred from the perspective of durability, such as mechanical strength and chemical resistance.
[0132] When the polyester film is a stretched film, the stretching method is not particularly limited, and can include longitudinal uniaxial stretching, transverse uniaxial stretching, longitudinal and transverse successive biaxial stretching, and simultaneous longitudinal and transverse biaxial stretching. When stretching polyester films, stretching can be performed before or after the lamination of the easily bondable resin layer (described later). Alternatively, uniaxial stretching can be performed longitudinally or transversely before laminating the easily bondable resin layer, and stretching can be performed in other directions after laminating the resin layer.
[0133] For example, it can be used to laminate polyimide film, polyamide film, polyamide-imide film, polycarbonate film, acrylic film, triacetyl cellulose film, cyclic olefin polymer film, polyphenylene sulfide film, polymethylpentene film, etc., onto at least one surface of the polyester film as the substrate.
[0134] It is desirable that the refractive index of the polyester film 11, which serves as the substrate, is higher than that of the functional layer 12. The refractive index of the polyester film 11, for example, can be determined using the Beck method. When determining the refractive index of the polyester film 11 using the Beck method, 10 fragments of the polyester film 11 are cut out. The refractive index of each of the 10 fragments is determined using a refractive index standard solution and the average of the 10 measured refractive indices is taken as the refractive index of the polyester film 11.
[0135] The refractive index of the polyester film 11, which serves as the substrate, can be between 1.500 and 1.800. Furthermore, the refractive index of the polyester film 11 can be determined by measuring the average reflectance at wavelengths of 380-780 nm using a spectrophotometer (product name "UV-2450", manufactured by Shimadzu Corporation), and then using the obtained average reflectance to calculate the reflectance using the following formula (1). The average reflectance (R) of the polyester film 11 serving as the substrate is measured as follows: To prevent back reflection, a black vinyl tape (e.g., product name "Yamato Vinyl Tape NO200-38-21", manufactured by Yamato Corporation, 38 mm wide) with a width greater than the area of the measurement spot is attached to the back of the polyester film 11 serving as the substrate, and then the measurement is performed.
[0136] R1=(1-n1) 2 / (1+n1) 2…(1)
[0137] In the above formula (1), R1 represents the average reflectance (%) of the polyester film used as the substrate at wavelengths of 380~780nm, and n1 represents the refractive index of the polyester film used as the substrate.
[0138] The thickness of the polyester film 11 as the substrate is preferably 10 μm or more and 100 μm or less. If the thickness of the polyester film as the substrate is 10 μm or more, curling of the optical film can be suppressed, and sufficient rigidity can be obtained. Furthermore, even when manufacturing the optical film by roll-to-roll, wrinkles are less likely to occur, eliminating concerns about deterioration of the appearance. On the other hand, if the thickness of the polyester film as the substrate is 100 μm or less, the optical film has good folding properties, meeting the conditions for continuous folding tests. Additionally, it is preferable in terms of lightweighting the optical film. The thickness of the polyester film 11 as the substrate is determined using a scanning electron microscope (SEM) by photographing a cross-section of the polyester film 11 as the substrate. The film thickness at 10 points in the cross-sectional image is measured, and the arithmetic mean of the film thickness at these 10 points is taken. The lower limit of the thickness of the polyester film 11 as the substrate is more preferably 25 μm or more, and the upper limit is more preferably 80 μm or less.
[0139] (Functional layer)
[0140] The optical thin film of the present invention has a functional layer 12 disposed on the first surface 11A side of the substrate 11.
[0141] Functional layer 12 is, for example, a layer that functions as a hard coating. In addition to its hard coating properties, functional layer 12 may also have other functions besides hard coating. In this specification, "hard coating" refers to a layer whose martensite hardness at the center of its cross-section is 375 MPa or higher. In this specification, "martensite hardness" refers to the hardness when an indenter is pressed into the sample at 500 nm using a hardness test based on nanoindentation. The above-mentioned martensite hardness test based on nanoindentation was performed on the test sample using a HYSITRON TI950 TriboIndenter. Specifically, first, a block is prepared by embedding an optical film cut to 1 mm × 10 mm using embedding resin. Uniform slices without pores and with a thickness of 70 nm or more and 100 nm or less are cut from this block using a conventional slicing method. Slice preparation can be performed using an "EM UC7 ultramicrotome" (Leica Microsystems Co., Ltd.). Then, the remaining block after cutting the uniform slice without pores is used as the test sample. Next, in the cross-section obtained by cutting the aforementioned slice from the sample, under the following measurement conditions, a Berkovich indenter (triangular pyramid) is used as the indenter to press 500 nm into the center of the functional layer cross-section, maintaining a constant pressure to relax the residual stress. Then, the load is removed, and the maximum load after relaxation is measured. This maximum load P is then used. max (μN) and the indentation area A (nm) with a depth of 500nm. 2 ), through P max / A calculates the martensitic hardness. The martensitic hardness is the arithmetic mean of the values obtained from measuring 10 locations.
[0142] (Measurement conditions)
[0143] • Loading speed: 10 nm / s
[0144] • Duration: 5 seconds
[0145] • Load removal speed: 10 nm / s
[0146] • Measurement temperature: 25℃
[0147] Regarding the functional layer 12, the martensite hardness at the center of its cross-section is preferably 500 MPa or more and 2000 MPa or less. If the martensite hardness of the functional layer 12 is 500 MPa or more, sufficient hardness can be obtained as a hard coating; conversely, if it is 2000 MPa or less, good folding properties of the optical thin film can be obtained. The lower limit of the martensite hardness at the center of the cross-section of the functional layer 12 is preferably 600 MPa or more, and the upper limit is preferably 1500 MPa or less.
[0148] The refractive index of the functional layer 12 can be 1.400 or higher and 1.800 or lower. The refractive index of the functional layer 12 can be determined by measuring the average reflectance at wavelengths of 380 to 780 nm using a spectrophotometer (product name "UV-2450", manufactured by Shimadzu Corporation), and by using the obtained average reflectance, by formula (2) below. The average reflectance of the functional layer 12 is measured as follows: a functional layer composition is coated on a 50 μm thick polyethylene terephthalate (PET) substrate without easy-bonding treatment, and cured to form a functional layer with a thickness of 1 to 10 μm. To prevent back reflection, a black vinyl tape (e.g., product name "Yamato Vinyl Tape NO200-38-21", manufactured by Yamato Corporation, 38 mm wide) with a width greater than the area of the measurement spot is attached to the side of the PET substrate opposite to the side of the functional layer (back side), and then the measurement is performed.
[0149] R² = (1 - n²) 2 / (1+n2) 2 …(2)
[0150] In the above formula (2), R2 represents the average reflectivity (%) of the functional layer at wavelengths of 380~780nm, and n2 represents the refractive index of the functional layer.
[0151] The thickness of the functional layer 12 is preferably 2 μm or more and 40 μm or less. If the thickness of the functional layer 12 is 2 μm or more, sufficient hardness can be obtained as a hard coating; conversely, if it is 40 μm or less, deterioration of processability can be suppressed. Regarding the "film thickness of the functional layer" in this specification, in the case of a multilayer structure, it refers to the total thickness obtained by summing the thicknesses of each functional layer. The upper limit of the thickness of the functional layer 12 is more preferably 30 μm or less, and even more preferably 20 μm or less. The film thickness of the functional layer 12 can be 2 μm or more and 30 μm or less, or 2 μm or more and 20 μm or less.
[0152] To determine the thickness of functional layer 12, a cross-section of functional layer 12 was photographed using a scanning transmission electron microscope (STEM) or a transmission electron microscope (TEM). The thickness of functional layer 12 at 20 points in the cross-sectional image was measured, and the arithmetic mean of the thicknesses at these 20 points was taken. The specific method for taking the cross-sectional photograph is described below. First, a block containing an optical film cut to size 1 mm × 10 mm was prepared by embedding it in embedding resin. Uniform slices without pores and with a thickness of 70 nm or more and 100 nm or less were cut from this block using conventional slicing methods. Slices can be prepared using an ultramicrotome such as the EM UC7 (Leica Microsystems Co., Ltd.). Then, this uniform slice without pores was used as the measurement sample. Finally, a cross-sectional photograph of the measurement sample was taken using a scanning transmission electron microscope (STEM) (product name "S-4800", manufactured by Hitachi High Technology Co., Ltd.). When using the S-4800 to capture cross-sectional photographs, the detector is set to "TE", the accelerating voltage to "30kV", and the emission current to "10μA" for cross-sectional observation. Regarding magnification, the focus is adjusted while observing whether the layers can be distinguished, and contrast and brightness are appropriately adjusted between 5000x and 200,000x. A preferred magnification is 10,000x to 100,000x, a further preferred magnification is 10,000x to 50,000x, and the most preferred magnification is 25,000x to 50,000x. It should be noted that when using the S-4800 to capture cross-sectional photographs, the aperture can also be set to "beam monitor stop 3", the objective stop to "3", and the WD to "8mm". When determining the thickness of the hard coating, it is crucial to observe the interface contrast between the functional layer and other layers (e.g., the polyester film as the substrate) as clearly as possible during cross-sectional observation. If the interface is difficult to see due to insufficient contrast, staining with osmium tetroxide, ruthenium tetroxide, or phosphotungstic acid can make the interface between organic layers easily visible, thus allowing for such staining. Furthermore, interface contrast can sometimes be difficult to discern at high magnification. In such cases, observation is also conducted at low magnification. For example, observations can be performed at two different magnifications: 25,000x and 50,000x, or 50,000x and 100,000x. The arithmetic mean of the results at both magnifications is then calculated, and this average is used as the film thickness of the functional layer.
[0153] The functional layer 12 may suitably be an antistatic hard coating, or it may contain an adhesive resin and an antistatic agent present in the adhesive resin. In addition to the adhesive resin, the functional layer 12 may, as needed and without impairing the effects of the present invention, contain additives such as inorganic particles, organic particles, ultraviolet absorbers, adhesion improvers, leveling agents, thixotropic agents, coupling agents, plasticizers, defoamers, fillers, colorants, and fillers.
[0154] (Adhesive resin)
[0155] Adhesive resins are polymers (cured products) comprising polymeric compounds (curing compounds). The polymeric compound has at least one polymeric functional group within its molecule. Examples of polymeric functional groups include olefinic unsaturated groups such as (meth)acryloyl, vinyl, and allyl. It should be noted that "(meth)acryloyl" includes both "acryloyl" and "methacryloyl".
[0156] Polyfunctional (meth)acrylates are preferred as polymerizable compounds. Examples of such polyfunctional (meth)acrylates include trimethylolpropane trimethacrylate, tripropylene glycol dimethacrylate, diethylene glycol dimethacrylate, dipropylene glycol dimethacrylate, pentaerythritol trimethacrylate, pentaerythritol tetramethacrylate, dipentaerythritol hexamethacrylate, 1,6-hexanediol dimethacrylate, neopentyl glycol dimethacrylate, trimethylolpropane trimethacrylate, bis(trimethylolpropane tetramethacrylate), and dipentaerythritol pentamethacrylate. Tripentaerythritol octa(meth)acrylate, tetrapentaerythritol deca(meth)acrylate, isocyanurate tri(meth)acrylate, isocyanurate di(meth)acrylate, polyester tri(meth)acrylate, polyester di(meth)acrylate, bisphenol di(meth)acrylate, diglycerol tetra(meth)acrylate, adamantyl di(meth)acrylate, isobornyl di(meth)acrylate, dicyclopentane di(meth)acrylate, tricyclodecane di(meth)acrylate, bis(trimethylolpropane tetra(meth)acrylate, and substances modified from them using PO, EO, caprolactone, etc.
[0157] Among these, substances with 3 to 6 functionalities are preferred from the perspective of suitably satisfying the aforementioned martensitic hardness, such as pentaerythritol triacrylate (PETA), dipentaerythritol hexaacrylate (DPHA), pentaerythritol tetraacrylate (PETTA), dipentaerythritol pentaacrylate (DPPA), trimethylolpropane tri(meth)acrylate, tripentaerythritol octa(meth)acrylate, and pentaerythritol deca(meth)acrylate. It should be noted that in this specification, "(meth)acrylate" refers to both "acrylate" and "methacrylate".
[0158] It should be noted that, in order to adjust the hardness, viscosity of the composition, and improve adhesion, etc., monofunctional (meth)acrylate monomers may be further included. Examples of the aforementioned monofunctional (meth)acrylate monomers include, for example, hydroxyethyl acrylate (HEA), glycidyl methacrylate, methoxy polyethylene glycol (meth)acrylate, isooctadecyl (meth)acrylate, 2-acryloyloxyethyl succinate, acrylmorpholine, N-acryloyloxyethyl hexahydrophthalimide, cyclohexyl acrylate, tetrahydrofurfuryl acrylate, isobornyl acrylate, phenoxyethyl acrylate, and adamantyl acrylate.
[0159] From the viewpoint of improving the hardness of the functional layer, the mass-average molecular weight of the aforementioned monomers is preferably less than 1000, more preferably 200 or more and 800 or less. Furthermore, the mass-average molecular weight of the aforementioned polymeric oligomers is preferably 1000 or more and 20,000 or less, more preferably 1000 or more and 10,000 or less, and even more preferably 2000 or more and 7000 or less.
[0160] (Antistatic agent)
[0161] There are no particular limitations on the antistatic agent used in functional layer 12, as long as it has good compatibility with the adhesive resin. As an antistatic agent, there are ion-conducting antistatic agents and electron-conducting antistatic agents. From the viewpoint of compatibility with the adhesive resin, ion-conducting antistatic agents are preferred.
[0162] The functional layer 12 may further include ultraviolet absorbers, spectral transmittance modifiers and / or antifouling agents.
[0163] (UV absorber)
[0164] Optical films are particularly suitable for mobile terminals such as foldable smartphones and tablets. However, these mobile terminals are mostly used outdoors. Therefore, there is a problem that polarizers, which are positioned closer to the display element than optical films, are easily degraded by exposure to ultraviolet light. However, since functional layer 12 is disposed on the observer side of the polarizer, if functional layer 12 contains an ultraviolet absorber, it is possible to appropriately prevent the polarizer from degrading due to exposure to ultraviolet light. It should be noted that the ultraviolet absorber (UVA) mentioned above may not be contained in functional layer 12, but may be contained in the polyester film 11, which serves as the substrate.
[0165] Examples of UV absorbers include triazine-based UV absorbers, benzophenone-based UV absorbers, and benzotriazole-based UV absorbers.
[0166] Examples of triazine-based ultraviolet absorbers include 2-(2-hydroxy-4-[1-octoxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine, 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, and 2,4-bis[2-hydroxy-4-butoxyphenyl] Triazine-based ultraviolet absorbers include 6-(2,4-dibutoxyphenyl)-1,3,5-triazine, 2-[4-[(2-hydroxy-3-tetrazoloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, and 2-[4-[(2-hydroxy-3-(2'-ethylhexyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, etc. Examples of commercially available triazine-based ultraviolet absorbers include TINUVIN460, TINUVIN477 (both manufactured by BASF), and LA-46 (manufactured by ADEKA).
[0167] Examples of benzophenone-based ultraviolet absorbers include 2-hydroxybenzophenone, 2,4-dihydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, hydroxymethoxybenzophenone sulfonic acid and its trihydrate, and sodium hydroxymethoxybenzophenone sulfonate. Commercially available benzophenone-based ultraviolet absorbers include CHMASSORB81 / FL (manufactured by BASF).
[0168] Examples of benzotriazole-based ultraviolet absorbers include 2-ethylhexyl-3-[3-tert-butyl-4-hydroxy-5-(5-chloro-2H-benzotriazole-2-yl)phenyl]propionate, 2-(2H-benzotriazole-2-yl)-6-(linear and side-chain dodecyl)-4-methylphenol, 2-[5-chloro(2H)-benzotriazole-2-yl]-4-methyl-6-(tert-butyl)phenol, 2-(2H-benzotriazole-2-yl)-4,6-di-tert-pentylphenol, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, and 2-(2'-hydroxy-3',5'-methylphenyl)benzotriazole. '-Di-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(3',4',5',6'-tetrahydrophthalimidemethyl)-5'-methylphenyl)benzotriazole, 2,2-methylenebis(4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazole-2-yl)phenol) and 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, etc. Commercially available benzotriazole-based ultraviolet absorbers include, for example, KEMISORB71D, KEMISORB79 (both manufactured by CHEMIPRO), JF-80, JAST-500 (both manufactured by Jōhoku Chemical Co., Ltd.), ULS-1933D (manufactured by Yonhap Chemical Co., Ltd.), and RUVA-93 (manufactured by Otsuka Chemical Co., Ltd.).
[0169] Among these, triazine-based and benzotriazole-based UV absorbers are suitable as UV absorbers. Preferably, the UV absorber has high solubility with the resin components constituting the functional layer, and also preferably exhibits minimal exudation after the aforementioned continuous folding test. The UV absorber is preferably polymerized or oligomerized. As a UV absorber, polymers or oligomers having a benzotriazole, triazine, or benzophenone backbone are preferred; specifically, substances obtained by thermally copolymerizing (meth)acrylates having a benzotriazole or benzophenone backbone with methyl methacrylate (MMA) in any ratio are preferred. It should be noted that when optical films are used in organic light-emitting diode (OLED) display devices, the UV absorber can also protect the OLED from UV radiation.
[0170] The content of the ultraviolet absorber is not particularly limited, but is preferably 1 part by mass or more and 6 parts by mass or less relative to 100 parts by mass of the solid components of the functional layer composition. If it is 1 part by mass or more, the effect of containing the ultraviolet absorber in the functional layer can be sufficiently obtained, and if it is 6 parts by mass or less, the functional layer will not experience significant coloring or strength reduction. The lower limit of the content of the ultraviolet absorber is more preferably 2 parts by mass or more, and the upper limit is more preferably 5 parts by mass or less. The content of the ultraviolet absorber relative to 100 parts by mass of the solid components of the functional layer composition can be 2 parts by mass or more and 6 parts by mass or 2 parts by mass or 5 parts by mass or less, etc.
[0171] There are no particular limitations on the benzotriazole monomers of the sesamol type mentioned above. Examples of specific names include 2-[2-(6-hydroxybenzo[1,3]dioxacyclopenten-5-yl)-2H-benzotriazole-5-yl]ethyl methacrylate, 2-[2-(6-hydroxybenzo[1,3]dioxacyclopenten-5-yl)-2H-benzotriazole-5-yl]ethyl methacrylate, 3-[2-(6-hydroxybenzo[1,3]dioxacyclopenten-5-yl)-2H-benzotriazole-5-yl]propyl methacrylate, 3-[2-(6-hydroxybenzo[1,3]dioxacyclopenten-5-yl)-2H-benzotriazole-5-yl]propyl methacrylate, 4-[2-(6-hydroxybenzo[1,3]dioxacyclopenten-5-yl)-2H-benzotriazole-5-yl]propyl methacrylate, and 4-[2-(6-hydroxybenzo[1,3]dioxacyclopenten-5-yl)-2H-benzotriazole-5-yl]ethyl methacrylate. [3]dioxacyclopenten-5-yl)-2H-benzotriazol-5-yl]butyl methacrylate, 4-[2-(6-hydroxybenzo[1,3]dioxacyclopenten-5-yl)-2H-benzotriazol-5-yl]butyl methacrylate, 2-[2-(6-hydroxybenzo[1,3]dioxacyclopenten-5-yl)-2H-benzotriazol-5-yloxy]ethyl methacrylate, 2-[2-(6-hydroxybenzo[1,3]dioxacyclopenten-5-yl)-2H-benzotriazol-5-yloxy]ethyl methacrylate, 2-[3-[2-(6-hydroxybenzo[1,3]dioxacyclopenten-5-yl)-2H-benzotriazol-5-yl]propionyloxy]ethyl methacrylate, 2- [3-[2-(6-hydroxybenzo[1,3]dioxacyclopenten-5-yl)-2H-benzotriazol-5-yl]propionyloxy]ethyl methacrylate, 4-[3-[2-(6-hydroxybenzo[1,3]dioxacyclopenten-5-yl)-2H-benzotriazol-5-yl]propionyloxy]butyl methacrylate, 4-[3-[2-(6-hydroxybenzo[1,3]dioxacyclopenten-5-yl)-2H-benzotriazol-5-yl]propionyloxy]butyl methacrylate, 2-[3-[2-(6-hydroxybenzo[1,3]dioxacyclopenten-5-yl)-2H-benzotriazol-5-yl]propionyloxy]ethyl methacrylate, 2-[3-[2-(6-hydroxybenzo[1,3]dioxacyclopenten-5-yl)-2H-benzotriazol-5-yl]propionyloxy]ethyl methacrylate, 2-[3-[2-(6-hydroxybenzo[1,3]dioxacyclopenten-5-yl)-2H-benzotriazol-5-yl]propionyloxy]ethyl methacrylate, Dioxacyclopenten-5-yl)-2H-benzotriazole-5-yl]propionoxy]ethyl acrylate, 2-(methacryloyloxy)ethyl 2-(6-hydroxybenzo[1,3]dioxacyclopenten-5-yl)-2H-benzotriazole-5-carboxylic acid ester, 2-(acryloyloxy)ethyl 2-(6-hydroxybenzo[1,3]dioxacyclopenten-5-yl)-2H-benzotriazole-5-carboxylic acid ester, 4-(methacryloyloxy)butyl 2-(6-hydroxybenzo[1,3]dioxacyclopenten-5-yl)-2H-benzotriazole-5-carboxylic acid ester, 4-(acryloyloxy)butyl-2-(6-hydroxybenzo[1,3]dioxacyclopenten-5-yl)-2H-benzotriazole-5-carboxylic acid ester, etc.In addition, one type of these sesamol-type benzotriazole monomers can be used, or two or more types can be used.
[0172] (Antifouling agent)
[0173] There are no particular limitations on the type of antifouling agent; examples include silicone-based, fluorinated, and silicone-and-fluorinated antifouling agents, which can be used individually or in combination. Additionally, acrylic-based antifouling agents can also be used.
[0174] The content of the antifouling agent is preferably 0.01 to 3.0 parts by mass relative to 100 parts by mass of the polymeric compound. If it is 0.01 parts by mass or more, sufficient antifouling properties can be imparted to the functional layer. In addition, if it is 3.0 parts by mass or less, the hardness of the functional layer will not decrease.
[0175] The antifouling agent preferably has a weight-average molecular weight of 5000 or less. To improve the durability of the antifouling performance, it is preferably a compound having one or more reactive functional groups, more preferably two or more. In particular, by using an antifouling agent having two or more reactive functional groups, excellent scratch resistance can be imparted.
[0176] When the antifouling agent does not have reactive functional groups, whether the optical film is in roll or sheet form, the antifouling agent will transfer to the back side of the optical film when it is overlapped. If other layers are to be attached or coated on the back side of the optical film, the other layers may peel off. In addition, there are cases where peeling is easy due to repeated continuous folding tests.
[0177] Furthermore, the antifouling properties of the aforementioned antifouling agents with reactive functional groups exhibit good durability. The functional layer containing the aforementioned fluorinated antifouling agent is less prone to fingerprint adhesion (less noticeable) and also has good wipeability. In addition, since it can reduce the surface tension during coating of the functional layer composition, it has good leveling properties, resulting in a good appearance of the formed functional layer.
[0178] The functional layer containing a silicone-based antifouling agent exhibits good sliding properties and resistance to steel wool. Touch sensors with this silicone-based antifouling agent-coated optical film on the functional layer show improved sliding when touched with fingers, pens, etc., thus enhancing the tactile experience. Furthermore, the functional layer is less prone to fingerprint adhesion (less noticeable) and has good wipeability. In addition, due to the reduced surface tension during coating of the functional layer with the composition, it exhibits good leveling properties, resulting in a pleasant appearance of the formed functional layer.
[0179] Commercially available silicone-based antifouling agents include, for example, SUA1900L10 (manufactured by Shin-Nakamura Chemical Co., Ltd.), SUA1900L6 (manufactured by Shin-Nakamura Chemical Co., Ltd.), Ebecryl1360 (manufactured by Daicel-Cytec Co., Ltd.), UT3971 (manufactured by Nippon Seizo Co., Ltd.), BYKUV3500 (manufactured by BYK-Chemie Co., Ltd.), BYKUV3510 (manufactured by BYK-Chemie Co., Ltd.), and BYKUV3570. (BYK-Chemie), X22-164E, X22-174BX, X22-2426, KBM503, KBM5103 (Shin-Etsu Chemical), TEGO-RAD2250, TEGO-RAD2300, TEGO-RAD2200N, TEGO-RAD2010, TEGO-RAD2500, TEGO-RAD2600, TEGO-RAD2700 (Evonik Japan), Megafac RS854 (DIC), etc.
[0180] Commercially available fluorinated antifouling agents include, for example, OPTOOL DAC, OPTOOL DSX (manufactured by Daikin Industries), Megafac RS71, Megafac RS74 (manufactured by DIC), LINC152EPA, LINC151EPA, LINC182UA (manufactured by Kyoei Chemicals), Ftergent 650A, Ftergent 601AD, and Ftergent 602.
[0181] Commercially available antifouling agents that are fluorine-based or organosilicon-based and have reactive functional groups include, for example, Megafac RS851, Megafac RS852, Megafac RS853, Megafac RS854 (manufactured by DIC), OPSTARTU2225, OPSTAR TU2224 (manufactured by JSR), and X71-1203M (manufactured by Shin-Etsu Chemical).
[0182] (Resin layer A)
[0183] The optical film of the present invention has a resin layer A13 disposed between the substrate 11 and the functional layer 12.
[0184] The resin layer A13 is, for example, a layer used to suppress the generation of interference fringes. From the viewpoint of suppressing interference fringes, the refractive index of the resin layer A13 is preferably lower than that of the polyester film 11, which serves as the substrate, and higher than that of the functional layer 12. The refractive index of the resin layer A13 can be measured using the same method as that used for the refractive index of the functional layer.
[0185] The difference in refractive index between resin layer A13 and functional layer 12 (e.g., the refractive index of resin layer A minus the refractive index of functional layer) is preferably 0.005 or more and 0.100 or less. If the difference in refractive index is 0.005 or more, it can be set to a level where, although interfacial reflection occurs between resin layer A13 and functional layer 12, interference fringes cannot be visually discerned. Conversely, if it is 0.100 or less, it can be set to a level where, although some interference fringes are detected, there is no problem in practical use. The lower limit of this difference in refractive index is more preferably 0.007 or more, and the upper limit is more preferably 0.090 or less. The refractive index of resin layer A13 can be 0.010 or more and 0.080 or less, 0.007 or more and 0.100 or less, 0.007 or more and 0.090 or less, 0.007 or more and 0.080 or less, etc.
[0186] The thickness of resin layer A13 is 10 nm or more and 500 nm or less, preferably 30 nm or more and 200 nm or less. If the thickness of resin layer A13 is 10 nm or more, sufficient adhesion between functional layer 12 and resin layer A13 can be ensured. Furthermore, if it is 500 nm or less, interference fringes can be further suppressed, and foldability can be improved. The thickness of resin layer A13 can be determined using the same method as for functional layer 12.
[0187] The resin layer A (13) is more preferably 50 nm or more, for example, more preferably 150 nm or less. The film thickness of the resin layer A13 can be 50 nm or more and 500 nm or less, 50 nm or more and 200 nm or less, or 50 nm or more and 150 nm or less.
[0188] Resin layer A13 may consist solely of resin, but preferably includes a binder resin and particles (A-4) for adjusting the refractive index. The binder resin of resin layer A13 is preferably at least one resin selected from the group consisting of (meth)acrylic resins, cellulose resins, urethane resins, vinyl chloride resins, polyester resins, polyolefin resins, polycarbonate, nylon, polystyrene, and ABS resins. The particles included in resin layer A13 can be inorganic particles or organic polymer particles. Examples of inorganic particles include titanium dioxide, barium sulfate, calcium carbonate, calcium sulfate, silica, alumina, zirconium oxide, talc, kaolin, clay, or mixtures thereof. Furthermore, they can be used in combination with other common inorganic particles, such as calcium phosphate, mica, lithium montmorillonite, tungsten oxide, lithium fluoride, and calcium fluoride. Examples of organic polymer particles include styrene-based, acrylic-based, melamine-based, benzoguanamine-based, and organosilicon-based polymer particles.
[0189] In one embodiment, the preferred material is at least one selected from the group consisting of low-refractive-index particles such as silica and magnesium fluoride, metal oxide particles such as titanium dioxide and zirconium oxide, and inorganic pigments such as cobalt blue. Among these, from the viewpoint of adjusting adhesion and the difference in refractive index, a combination of polyester resin and metal oxide particles such as titanium dioxide and zirconium oxide can be used.
[0190] The adhesive resin constituting resin layer A13 is a resin with easy adhesion, including polycarbonate polyurethane resin, which is a urethane resin with a polycarbonate structure, and polyester resin. By employing a resin layer composed of these resins, the adhesion between the polyester film substrate and the functional layer is significantly improved.
[0191] In one embodiment, resin layer A is a cured layer of a curable resin composition comprising a polycarbonate polyurethane resin (A-1), a polyester resin (A-2), a capped isocyanate crosslinking agent (A-3), and particles (A-4), wherein the polyester resin (A-2) has a fused polycyclic aromatic structure. By giving resin layer A such a composition, the generation of interference light can be suppressed, and furthermore, an optical film that does not crack or break under repeated 10,000 180° folding tests can be obtained.
[0192] In particular, in this invention, the adhesion between the polyester film substrate and the functional layer is significantly improved by having resin layer A. Therefore, when an impact is applied to the surface of the optical film, not only can the deformation of the optical film itself be suppressed, but also the plastic deformation of the adhesive layer can be suppressed even when the adhesive layer is disposed in a part closer to the inside of the image display device than the optical film. In addition, the breakage of the optical film during folding can be suppressed.
[0193] Furthermore, it exhibits excellent resilience when folded, held in place, and then unfolded again.
[0194] In particular, it was confirmed that by making resin layer A a cured layer of a curable resin composition comprising polycarbonate polyurethane resin (A-1), polyester resin (A-2), end-capped isocyanate crosslinking agent (A-3), and particles (A-4), stable adhesion to the functional layer can be ensured. The stability referred to here includes long-term adhesion stability, stability under humid and hot conditions, and adhesion stability after bending tests, etc., ensuring that the functional layer adheres tightly without peeling before and after treatment.
[0195] The resin layer A of the present invention exhibits good compatibility with the composition of the functional layer described later. Furthermore, the functional layer, obtained by UV curing under UV irradiation, has a cross-linked mesh structure. The polycarbonate polyurethane resin and polyester resin in the resin layer interact with each other, readily fusing and entangled. Moreover, it is believed that by intertwining these intertwined resins with the mesh structure of the functional layer formed thereon, a resin layer with superior adhesion compared to previous methods is achieved. Furthermore, since the resin layer contains polyester resin, its adhesion to the polyester film serving as the substrate is also improved, resulting in a resin layer with even superior adhesion.
[0196] Polycarbonate polyurethane resin is not particularly limited to any urethane resin with a polycarbonate structure in its molecule. It is a resin obtained by addition reaction of polycarbonate diol, diisocyanate, and diol as a chain extender as needed.
[0197] Examples of diols used in the preparation of polycarbonate polyurethane resins include ethylene glycol, propylene glycol, hexamethylene glycol, neopentyl glycol, 1,2-cyclohexanediethanol, 1,4-cyclohexanediethanol, 1,4-cyclohexanediethanol, decamethyl glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 2,2-bis(4-hydroxyphenyl)propane, and bis(4-hydroxyphenyl)sulfone. Among these, 1,2-cyclohexanediethanol, 1,4-cyclohexanediethanol, 1,4-cyclohexanediethanol, and 1,6-hexanediol are particularly preferred. Furthermore, these diols can be used alone or in combination of two or more. The ratio when combining two or more is not particularly limited and can be adjusted to obtain a polycarbonate polyurethane with the desired properties.
[0198] Examples of diisocyanate components required for the preparation of polycarbonate polyurethane resins include toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, phenyl dimethyl diisocyanate, naphthalene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, 4,4-methylene dicyclohexyl diisocyanate, 1,2-bis(isocyanate methyl)cyclohexane, and 1,4-bis(isocyanate methyl)cyclohexane. Among these, isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, 4,4-methylene dicyclohexyl diisocyanate, 1,2-bis(isocyanate methyl)cyclohexane, and 1,4-bis(isocyanate methyl)cyclohexane are particularly preferred, as they have a structure in which at least one hydrogen atom on the cyclohexane ring is substituted with a hydrocarbon group. Furthermore, these isocyanate components can be used alone or in combination of two or more. There is no particular limitation on the ratio when combining two or more; it can be adjusted to obtain a polycarbonate polyurethane with the desired properties.
[0199] Polyester resin is formed by the condensation polymerization of dicarboxylic acid and diol components. There are no particular limitations as long as it is a copolyester formed from dicarboxylic acid and diol components; one or more dicarboxylic acid and diol components can be used. In this invention, it is particularly preferred that the dicarboxylic acid component has a structure containing a naphthalene ring.
[0200] Examples of dicarboxylic acid components include terephthalic acid, isophthalic acid, phthalic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, diphenylcarboxylic acid, diphenoxyethanedicarboxylic acid, diphenylsulfonecarboxylic acid, anthracene dicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, hexahydroterephthalic acid, hexahydroisophthalic acid, malonic acid, dimethylmalonic acid, cyclohexylmethylmalonic acid, succinic acid, 3,3-diethylsuccinic acid, cyclohexylmethylsuccinic acid, glutaric acid, 2,2-dimethylglutaric acid, adipic acid, 2-methyl adipic acid, trimethyl adipic acid, pimelic acid, azelaic acid, dimer acid, sebacic acid, octanoic acid, dodecanedicarboxylic acid, and 1,1-cyclohexanediacetic acid. Among them, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, and 1,5-naphthalenedicarboxylic acid have the above-mentioned structure containing a naphthalene ring, and are particularly preferred.
[0201] Examples of diols include ethylene glycol, propylene glycol, hexamethylene glycol, neopentyl glycol, 1,2-cyclohexanediethanol, 1,4-cyclohexanediethanol, 1,4-cyclohexanediethanol, decamethyl glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 2,2-bis(4-hydroxyphenyl)propane, and bis(4-hydroxyphenyl)sulfone.
[0202] The ratio of the dicarboxylic acid component to the diol component is not particularly limited and can be adjusted in a way that yields a polyester with the desired properties.
[0203] In particular, in this invention, the polyester resin (A-2) preferably has a fused polycyclic aromatic structure. By giving the polyester resin (A-2) a fused polycyclic aromatic structure, the interaction with the functional layer is enhanced, and the adhesion to the functional layer is significantly improved. Therefore, it can be confirmed that the adhesion to the functional layer can be stably ensured. The stability referred to here includes long-term adhesion stability, stability under humid and hot conditions, and adhesion stability after bending tests, etc., achieving an effect where the functional layer adheres tightly without peeling before and after treatment.
[0204] For example, resin layers A, B, and C each contain at least one polyester resin (A-2), (B-2), and (C-2) with a fused polycyclic aromatic structure, each containing a naphthalene skeleton in its molecule. By having a naphthalene skeleton in the molecule, the interaction with the functional layer is enhanced, resulting in a significant improvement in the adhesion to the functional layer. Therefore, it can be confirmed that stable adhesion to the functional layer can be ensured. This stability refers to long-term adhesion stability, stability under humid and hot conditions, and adhesion stability after bending tests, achieving an effect where the functional layer adheres tightly without peeling before and after treatment.
[0205] The exact mechanism by which the polycarbonate polyurethane resin and polyester resin used in the resin layer exhibit the effects of the present invention is not yet clear. However, the resin layer of the present invention can improve the flexibility of the resin while maintaining its rigidity, thus performing its function optimally as a resin layer. That is, it not only has excellent adhesion to the substrate, such as polyester film and functional layer, but also significantly improves adhesion over time. As a result, a film that maintains its quality for a long time can be obtained.
[0206] In this invention, it is important that the adhesive resin comprises polycarbonate polyurethane resin and polyester resin. The ratio of the two is not particularly limited as long as it ensures the physical properties of the resulting resin layer. When the total amount of the adhesive resin is set to 100% by mass, the polycarbonate polyurethane resin is generally preferably 40% by mass or more and 85% by mass or less, more preferably 45% by mass or more and 80% by mass or less, and even more preferably 50% by mass or more and 75% by mass or less. By making the polycarbonate polyurethane resin 40% by mass or more, a balance between the softness and hardness of the urethane resin can be ensured, thus ensuring good adhesion over time. Furthermore, by setting it to 85% by mass or less, a balance between the hardness and softness of the resin layer can be maintained, and softness can also be improved, thus allowing the resin layer to function optimally.
[0207] (Cross-linking agent)
[0208] In this invention, a crosslinking agent can be included in the composition used to form the resin layer in order to form a crosslinked structure between the resins. By including a crosslinking agent, the adhesion under high temperature and high humidity conditions can be further improved. Specific crosslinking agents include, for example, urea-based, epoxy-based, melamine-based, isocyanate-based, oxazoline-based, and carbodiimide-based crosslinking agents. Among these, isocyanate-based crosslinking agents are preferred from the viewpoint of improving the stability of the coating liquid over time and the effect of improving adhesion under high temperature and high humidity conditions. Furthermore, a catalyst or the like can be used as needed to promote the crosslinking reaction.
[0209] When the composition for forming the resin layer includes an adhesive resin and a crosslinking agent, and the total mass of the adhesive resin and the crosslinking agent is set to 100% by mass, from the viewpoint of adhesion, the content of the adhesive resin is preferably 50-95% by mass, more preferably 55-90% by mass, further preferably 60-90% by mass, and most preferably 80-90% by mass. If it is 95% by mass or less, the strength of the resin layer coating is maintained, and the adhesion under high temperature and high humidity is good. If it is 50% by mass or more, the flexibility of the resin layer is maintained, and the adhesion under normal temperature, high temperature and high humidity is maintained, which is preferred. In addition, when the total mass of the adhesive resin and the crosslinking agent is set to 100% by mass, the content of the crosslinking agent is preferably 5-50% by mass, more preferably 10-45% by mass, further preferably 10-40% by mass, and most preferably 10-20% by mass.
[0210] When using isocyanate-based crosslinking agents, end-capping agents are suitable for controlling the reactivity of isocyanates. Examples of end-capping agents include: bisulfite compounds such as sodium bisulfite; pyrazole compounds such as 3,5-dimethylpyrazole, 3-methylpyrazole, 4-bromo-3,5-dimethylpyrazole, and 4-nitro-3,5-dimethylpyrazole; phenols such as phenol and cresol; aliphatic alcohols such as methanol and ethanol; active methylene compounds such as dimethyl malonate and acetylacetone; thiols such as butyl mercaptan and dodecyl mercaptan; amides such as acetanilide and acetamide; lactams such as ε-caprolactam and δ-valeractam; imides such as succinimide and maleimide; oximes such as acetaldehyde oxime, acetone oxime, and methyl ethyl ketone oxime; and amines such as diphenylaniline, aniline, and ethyleneimine. From a reactivity point of view, end-capping agents with pyrazole backbones are suitable for this system.
[0211] From the viewpoint of imparting water dispersibility in aqueous solvents, it is preferable to introduce hydrophilic groups into the end-capped isocyanate-based crosslinking agent. Furthermore, as hydrophilic groups, anionic groups such as carboxyl or sulfonic acid groups, and nonionic groups such as oxyalkyl groups are preferred. Crosslinking agents having these hydrophilic groups can be prepared by reacting a polyisocyanate, which is the base of the end-capped isocyanate, with a compound having hydrophilic groups and reactive groups such as hydroxyl groups.
[0212] (additive)
[0213] In the resin layer of this invention, known additives may be added without impairing the effects of the invention, such as surfactants, antioxidants, heat stabilizers, weather stabilizers, ultraviolet absorbers, organic slip agents, pigments, dyes, organic or inorganic particles, antistatic agents, nucleating agents, etc. However, it is preferable not to use substances that are environmentally unfriendly.
[0214] To further improve the anti-blocking properties of the resin layer, adding inactive particles to the resin layer is also a preferred method. Examples of particles contained in the resin layer include inorganic particles and organic polymer-based particles. Examples of inorganic particles include titanium dioxide, barium sulfate, calcium carbonate, calcium sulfate, silica, alumina, talc, kaolin, clay, or mixtures thereof. Furthermore, they can be used in combination with other common inorganic particles, such as calcium phosphate, mica, lithium montmorillonite, zirconium oxide, tungsten oxide, lithium fluoride, and calcium fluoride. Examples of organic polymer-based particles include styrene-based, acrylic-based, melamine-based, benzoguanamine-based, and organosilicon-based polymer-based particles.
[0215] The average particle size (average particle size based on the number of SEM images, hereinafter the same) of the inactive particles in the resin layer is preferably 0.01 to 20 μm, more preferably 0.04 to 2.0 μm, and even more preferably 0.1 to 1.0 μm. When the average particle size of the inactive particles is 0.04 μm or more, it is easy to form unevenness on the surface of the resin layer, thus improving the operability of the easily bondable polyester film, such as its sliding and winding properties, and improving the processability during lamination, which is therefore preferred. On the other hand, when the average particle size of the inactive particles is 2.0 μm or less, particle shedding is less likely to occur, which is also preferred. The particle concentration in the resin layer is preferably 1 to 20% by mass relative to the resin composition.
[0216] To achieve antistatic properties, resin layer A13 may contain an antistatic agent. When resin layer A13 contains an antistatic agent, it also functions as an antistatic layer. By including an antistatic agent in resin layer A13, the surface resistance of the surface 10A of the optical thin film 10 can be further stabilized. If functional layer 12 also contains an antistatic agent when resin layer A13 contains an antistatic agent, the surface resistance of the surface 10A of the optical thin film 10 can be further stabilized. The same antistatic agent described in the section on functional layer 12 can be used as the antistatic agent contained in resin layer A13, and therefore its description is omitted here.
[0217] (Composition for resin layer A)
[0218] The composition for resin layer A may include known materials without impairing the problem-solving and effects of the present invention.
[0219] (Resin layer B)
[0220] The optical film of the present invention may have a resin layer B15 disposed on a second side 11B of the substrate 11 opposite to the first side 11A.
[0221] Resin layer B15 is a layer that improves the light transmittance of optical film 10. The refractive index of resin layer B15 is higher than that of air (1.000) and lower than that of polyester film 11, which serves as the substrate. The refractive index of resin layer B15 can be measured using the same method as that used for the refractive index of functional layer 12, and therefore will not be described here.
[0222] The difference in refractive index between the polyester film 11 (the refractive index of the polyester film as the substrate) and the resin layer B15 (the refractive index of the resin layer B) is preferably 0.005 or higher and 0.700 or lower. If this refractive index difference is 0.005 or higher, the light transmittance of the optical film 10 can be improved; conversely, if it is 0.700 or lower, the transparency of the optical film 10 will not be impaired. The lower limit of this refractive index difference is more preferably 0.010 or higher, and the upper limit is more preferably 0.600 or lower. The refractive index of the resin layer B15 can be 0.050 or higher and 0.500 or lower.
[0223] The thickness of the resin layer B15 is 1 nm or more and 200 nm or less, preferably 10 nm or more and 180 nm or less, for example 30 nm or more and 150 nm or less.
[0224] If the thickness of the resin layer B15 is 1 nm or more and 200 nm or less, the transmittance of the optical thin film 10 can be further improved. For example, if it is also 200 nm or less, the deterioration of processability can be suppressed.
[0225] The thickness of resin layer B15 can be determined using the same method as functional layer 12.
[0226] The composition of resin layer B15 is not particularly limited as long as it is a layer with a refractive index higher than 1.000 and lower than that of the polyester film 11 serving as the substrate. Resin layer B15 can be composed of resin. In addition to resin, resin layer B15 may also contain low-refractive-index particles having a lower refractive index than the resin to further reduce the refractive index. Furthermore, to obtain antistatic properties, resin layer B15 may contain an antistatic agent. When resin layer B15 contains an antistatic agent, it also functions as an antistatic layer. Moreover, to adjust the hue of the optical film 10, resin layer B15 may contain hue modifiers such as spectral transmittance modifiers.
[0227] Spectral transmittance modifiers are used to adjust the spectral transmittance of optical films. For example, by including a sesamol-type benzotriazole monomer in resin layer C, the spectral transmittance can be appropriately adjusted.
[0228] Resin layer B is a cured layer of a curable resin composition formed from a composition comprising polycarbonate polyurethane resin (B-1), polyester resin (B-2), end-capped isocyanate crosslinking agent (B-3), and particles (B-4). In resin layer B, polyester resin (B-2) may have a fused polycyclic aromatic structure.
[0229] Details of these components can be found in the description of resin layer A13. The components contained in resin layer A and resin layer B may be the same or different.
[0230] The adhesive resin constituting resin layer B15 is a resin with easy adhesion, including polycarbonate polyurethane resin, which is a urethane resin with a polycarbonate structure, and polyester resin. By employing a resin layer composed of these resins, the adhesion between the polyester film substrate and resin layer B is significantly improved.
[0231] The reason for this is the good compatibility between the resin layer and the functional layer described later. Furthermore, the functional layer, obtained by UV curing via UV irradiation, has a cross-linked mesh structure. The polycarbonate polyurethane resin and polyester resin in the resin layer interact with each other, easily fusing and entangled. Moreover, it is believed that by intertwining these intertwined resins with the mesh structure of the functional layer formed thereon, a resin layer with superior adhesion compared to previous methods is achieved. Furthermore, since the resin layer contains polyester resin, its adhesion to the polyester film as the substrate is also improved, resulting in a resin layer with even superior adhesion.
[0232] Furthermore, by including a dicarboxylic acid component with a structure containing a naphthalene ring in the polyester resin used, it was found that not only could it improve light transmittance, but it was also confirmed that its adhesion to the adhesive layer disposed on the opposite side of the substrate was also improved.
[0233] Resin layer B15 may consist of resin alone, but preferably includes binder resin and particles for adjusting the refractive index. The composition of resin layer B15 can be prepared by the same method as that used for resin layer A13 described above, and can be obtained by preparing the composition for resin layer B in the same manner as the composition for resin layer A.
[0234] (Resin layer C)
[0235] In one manner, for example, such as Figure 4 As shown, resin layer C14 is disposed between substrate 11 and resin layer A13. Resin layer C14 is primarily used to improve the adhesion between resin layer A13 and the polyester film 11, which serves as the substrate, without generating interference fringes. It should be noted that regarding... Figure 4 A more detailed explanation follows.
[0236] By providing a resin layer C14 between the polyester film 11 as a substrate and the resin layer A13, the adhesion can be improved compared to the case where the resin layer A13 is in direct contact with the polyester film 11 as a substrate.
[0237] From the viewpoint of interference fringes, the refractive index of resin layer C14 is preferably lower than that of the polyester film 11, which serves as the substrate, and higher than that of resin layer A13. The refractive index of resin layer C14 can be measured using the same method as that of functional layer 12.
[0238] The refractive index difference between resin layer C14 and resin layer A13 (refractive index of resin layer C - refractive index of resin layer A) is preferably 0.005 or more and 0.100 or less. If the refractive index difference is 0.005 or more, it can be set to a level where, although interfacial reflection occurs between resin layer C14 and resin layer A13, interference fringes cannot be visually discerned. Conversely, if it is 0.100 or less, it can be set to a level where, although some interference fringes are detected, there is no problem in practical use. The lower limit of this refractive index difference is more preferably 0.007 or more, and the upper limit is more preferably 0.090 or less. The refractive index of resin layer A13 can be 0.010 or more and 0.080 or less.
[0239] The thickness of resin layer C14 is preferably 30 nm or more and 200 nm or less. If the thickness of resin layer C14 is 30 nm or more, sufficient adhesion between resin layer A13 and resin layer C14, as well as between the polyester film 11 (as a substrate) and resin layer C14, can be ensured. Furthermore, if the thickness is 200 nm or less, interference fringes will not occur due to the difference in refractive index between resin layer C14 and resin layer A13, and foldability can be improved. The thickness of resin layer C14 can be determined using the same method as for functional layer 12. The lower limit of resin layer C14 is more preferably 50 nm or more, and the upper limit is more preferably 150 nm or less. The thickness of resin layer C14 can be 50 nm or more and 200 nm or less, 30 nm or more and 150 nm or less, 50 nm or more and 150 nm or less, etc.
[0240] Resin layer C14 may consist of resin alone, but preferably includes binder resin and particles for adjusting the refractive index. The composition of resin layer C14 can be prepared by the same method as that used for resin layer A13 described above, and can be obtained by preparing the composition for resin layer C in the same manner as the composition for resin layer A. The various components contained in resin layers A, B, and C may be the same or different.
[0241] (Methods for manufacturing optical thin films)
[0242] As an example, a method for manufacturing an optical thin film having a resin layer C will be described.
[0243] The optical thin film 10 can be manufactured, for example, as follows. First, a composition for forming resin layer C for forming resin layer C14 is coated on the first side 11A of the polyester film 11, which serves as a substrate, using a coating apparatus such as a bar coater, to form a coating film of the composition for forming resin layer C.
[0244] After forming a coating film of the composition for resin layer C, the coating film is heated at a temperature of, for example, 40°C or higher and 200°C or lower for 10 to 120 seconds using various known methods, thereby drying it, evaporating or curing the solvent, and, as needed, irradiating the coating film with ionizing radiation such as ultraviolet light to form a resin layer C14 on a polyester film 11 as a substrate.
[0245] Next, using a coating apparatus such as a bar coater, a resin layer A composition for forming resin layer A13 is coated onto resin layer C14 to form a coating film of resin layer A composition.
[0246] After forming a coating film of the composition for resin layer A, the coating film is heated at a temperature of, for example, 40°C or higher and 200°C or lower for 10 to 120 seconds using various known methods, thereby drying it, evaporating or curing the solvent, and, as needed, irradiating the coating film with ionizing radiation such as ultraviolet light to form resin layer A13.
[0247] After forming the resin layer A13, a functional layer composition for forming the functional layer 12 is coated onto the resin layer A13 using a coating apparatus such as a bar coater, thereby forming a coating film of the functional layer composition. Thus, the method for manufacturing the optical thin film of the present invention includes manufacturing the functional layer 12 on the first surface 11A side of a polyester film 11, which serves as a substrate, through a coating process.
[0248] <Composition for Functional Layers>
[0249] The functional layer composition contains a polymeric compound that becomes an adhesive resin after curing. In addition, the functional layer composition may, as needed, contain antistatic agents, ultraviolet absorbers, spectral transmittance modifiers, antifouling agents, inorganic particles, leveling agents, solvents, and polymerization initiators.
[0250] (solvent)
[0251] Examples of solvents mentioned above include alcohols (e.g., methanol, ethanol, propanol, isopropanol, n-butanol, sec-butanol, tert-butanol, benzyl alcohol, PGME, ethylene glycol, diacetone alcohol), ketones (e.g., acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, heptanone, diisobutyl ketone, diethyl ketone, diacetone alcohol), esters (methyl acetate, ethyl acetate, butyl acetate, n-propyl acetate, isopropyl acetate, methyl formate, PGMEA), aliphatic hydrocarbons (e.g., hexane, cyclohexane), halogenated hydrocarbons (e.g., dichloromethane, chloroform, carbon tetrachloride), aromatic hydrocarbons (e.g., benzene, toluene, xylene), amides (e.g., dimethylformamide, dimethylacetamide, N-methylpyrrolidone), ethers (e.g., diethyl ether, dioxane, tetrahydrofuran), ether alcohols (e.g., 1-methoxy-2-propanol), and carbonates (dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate). These solvents can be used alone or in combination of two or more. Among these, methyl isobutyl ketone and methyl ethyl ketone are preferred as solvents, from the viewpoint of dissolving or dispersing the components such as urethane (meth) acrylate and other additives, so as to be suitable for coating the composition of the functional layer.
[0252] (Polymerization initiator)
[0253] Polymerization initiators are components that are decomposed by ionizing radiation and generate free radicals, thereby initiating or carrying out the polymerization (crosslinking) of polymerizable compounds.
[0254] The polymerization initiator is not particularly limited as long as it can release a substance that initiates free radical polymerization upon irradiation with ionizing radiation. There are no particular limitations on the polymerization initiator; known polymerization initiators can be used, such as acetophenones, benzophenones, Michaelis-Menten benzoylbenzoate, α-pentyl oxime ester, thioxanones, phenylacetones, benzoin derivatives, benzoyl compounds, and phosphine oxides. Furthermore, it is preferable to use it in combination with a photosensitizer; examples of such combinations include n-butylamine, triethylamine, and polyn-butylphosphine.
[0255] After forming a coating film of the composition for the functional layer, the coating film is heated at a temperature of, for example, above 30°C and below 120°C for 10 to 120 seconds using various known methods, thereby drying it and causing the solvent to evaporate.
[0256] After the coating film dries, it is irradiated with ionizing radiation such as ultraviolet light to cure it. This forms a functional layer 12 adjacent to the resin layer A13.
[0257] After the functional layer 12 is formed, a resin layer B composition for forming resin layer B15 is coated on the second side 11B of the polyester film 11, which serves as the substrate, using a coating apparatus such as a bar coater, to form a coating film of the resin layer B composition.
[0258] After forming a coating film of the resin layer B using the composition, the coating film is heated at a temperature of, for example, 40°C or higher and 200°C or lower for 10 to 120 seconds using various known methods to dry it, thereby evaporating or curing the solvent. In addition, the coating film is irradiated with ionizing radiation such as ultraviolet light as needed to form a resin layer B15. Thus, an optical thin film 10 of one type is obtained.
[0259] As an optical thin film used in an image display device, for example, it can be Figure 4 The optical thin film shown. In Figure 4 In some cases, it can also be folded. In one embodiment, the optical film of the present invention may be configured to further have an adhesive layer. For example, an adhesive layer 41 may be further provided on the second side 11B of the polyester film 11, which is the opposite side to the first side 11A.
[0260] Alternatively, the substrate may be comprised of a polyester film 11, a resin layer B15, and an adhesive layer 41. By placing the resin layer B between the substrate 11 and the adhesive layer 41, the effects of the invention can be achieved more effectively.
[0261] Figure 4 The optical film shown has a polyester film 11 as a substrate, and a resin layer C14, a resin layer A13, and a functional layer 12 are sequentially provided on the first surface 11A of the polyester film 11 as the substrate. In addition, a resin layer B15 and an adhesive layer 41 are sequentially provided on the second surface 11B of the polyester film 11 as the substrate.
[0262] As another way, from Figure 4 The optical thin film formed after removing the C14 resin layer in its composition ( Figure 5 It is also used as an image display device, and it is foldable.
[0263] The shear storage modulus G' of the optical thin film with an adhesive layer can exceed 200 MPa and be less than 1200 MPa in the frequency region of 25°C and 500 Hz to 1000 Hz. If the shear storage modulus G' of the film exceeds 200 MPa, then when an impact is applied to the surface of the optical thin film, not only can the deformation of the optical thin film itself be suppressed, but also the plastic deformation of the adhesive layer can be suppressed even when the adhesive layer is disposed in a part closer to the inside of the image display device than the optical thin film. In addition, if the shear storage modulus G' of the optical thin film with the adhesive layer is less than 1200 MPa, then the breakage of the optical thin film during folding can be suppressed. The lower limit of the shear storage modulus G' of the optical thin film is preferably 400 MPa or more, and more preferably 500 MPa or more. By setting such a lower limit, better impact resistance can be obtained. The upper limit of the shear storage modulus G' of the optical thin film is preferably less than 800 MPa. By setting such an upper limit, good recovery can be obtained when it is held after folding and then unfolded again. The shear storage modulus G' of the optical thin film can be above 400MPa and below 1200MPa, above 400MPa and below 800MPa, above 500MPa and below 1200MPa, above 500MPa and below 800MPa, etc.
[0264] The shear loss modulus G” of the optical thin film with the adhesive layer can be 3 MPa or more and 150 MPa or less in the frequency region of 25°C and 500 Hz or more and 1000 Hz or less. If the shear loss modulus G” of the optical thin film is 3 MPa or more, the reduction in impact absorption performance can be suppressed. In addition, if the shear loss modulus G” of the optical thin film with the adhesive layer is 150 MPa or less, the reduction in hardness of the adhesive layer 41 can be suppressed. The lower limit of the shear loss modulus G” of the optical thin film with the adhesive layer is preferably 20 MPa or more, and from the viewpoint of thinning the optical thin film, the upper limit of the shear loss modulus G” of the optical thin film is preferably 130 MPa or less, more preferably 100 MPa or less. The shear loss modulus G” of the optical thin film can be 20 MPa or more and 150 MPa or less, 20 MPa or more and 130 MPa or less, 20 MPa or more and 100 MPa or less, etc.
[0265] The shear storage modulus G' and shear loss modulus G” can be measured using a dynamic viscoelasticity measuring device (DMA). When measuring the shear storage modulus G' and shear loss modulus G” of an optical thin film using the DMA, firstly, the optical thin film with the adhesive layer is punched into a 10mm × 5mm rectangular shape to obtain a sample. Then, two of these samples are prepared and mounted on an optional solid shear fixture for the DMA (product name "Rheogel-E4000", manufactured by UBM). Specifically, the solid shear fixture has a 1mm thick metal solid shear plate (middle plate) and two L-shaped metal parts (outer plates) disposed on both sides of the solid shear plate. One sample is held between the solid shear plate and one of the L-shaped metal parts, and the other sample is held between the solid shear plate and the other L-shaped metal part. In this case, the sample is held with the resin layer on the solid shear plate side and the functional layer on the L-shaped metal part side. Then, the L-shaped metal parts are fastened together with screws to secure the sample. Next, after installing a tensile testing chuck consisting of an upper and lower chuck on the dynamic viscoelasticity measuring apparatus (product name "Rheogel-E4000", manufactured by UBM), a solid shearing fixture was installed between the upper and lower chucks at a chuck distance of 20 mm. The chuck distance is the distance between the upper and lower chucks. Then, the set temperature was set to 25°C, and the temperature was increased at a rate of 2°C / min. In this state, while fixing a solid shear plate, longitudinal vibrations with a strain of 1% and a frequency range of 500Hz to 1000Hz are applied to two L-shaped metal parts. Simultaneously, dynamic viscoelasticity measurements of the solid are performed at 25°C, and the shear storage modulus G' and shear loss modulus G'" of the optical thin film are measured. Here, the shear storage modulus G' and shear loss modulus G'" in the frequency range of 500Hz to 1000Hz for the optical thin film are set to the following values: longitudinal vibrations at frequencies of 500Hz, 750Hz, and 950Hz are applied to the L-shaped metal parts, and the shear storage modulus G' and shear loss modulus G'" of the optical thin film are measured at each frequency. The arithmetic mean of these shear storage modulus G' and shear loss modulus G'" is calculated. This measurement is repeated three times, and the three arithmetic mean values are further arithmetically averaged to obtain the final value. It should be noted that the frequency range of 500Hz and below 1000Hz is defined as follows: the frequency range is the frequency at which the surface of the optical film deforms by several micrometers to tens of micrometers when an object is dropped from a height of several centimeters, and it is also the frequency at which the optical film causes damage to the display panel and other components inside the image display device.
[0266] The physical properties of the optical thin film with the adhesive layer are the same as those of the optical thin film 10, except as described above, and may vary depending on the properties of the adhesive layer.
[0267] (Adhesive layer)
[0268] The adhesive layer 41 is a layer formed of a light-transmitting resin. The adhesive layer 41 is also an impact-absorbing layer. The adhesive layer can be a multilayer structure formed of two or more resin layers (e.g., a two-layer structure, a three-layer structure, a four-layer structure, etc.).
[0269] The thickness of the adhesive layer 41 can be 25 μm or more and 300 μm or less. If the thickness of the adhesive layer 41 is 25 μm or more, the decrease in hardness of the adhesive layer 41 can be suppressed. Furthermore, if it is 300 μm or less, thinner profiles can be achieved without deteriorating processability. Regarding the thickness of the adhesive layer 41, a cross-section of the adhesive layer 41 is photographed using a scanning electron microscope (SEM), and the thickness of the adhesive layer 41 at 20 points in the image is measured. The arithmetic mean of the thicknesses at these 20 points is taken. The lower limit of the adhesive layer 41 is more preferably 60 μm or more, and the upper limit of the adhesive layer 41 is preferably 200 μm or less, more preferably 150 μm or less, and even more preferably 100 μm or less. The thickness of the adhesive layer can be greater than 25μm and less than 200μm, greater than 25μm and less than 150μm, greater than 25μm and less than 100μm, greater than 50μm and less than 300μm, greater than 50μm and less than 200μm, greater than 50μm and less than 150μm, greater than 50μm and less than 100μm, etc.
[0270] The resin constituting the adhesive layer 41 is not particularly limited as long as the optical film having the adhesive layer has a shear storage modulus G' and shear loss modulus G" within the above-mentioned range in the frequency region of 25°C and 500Hz to 1000Hz. Examples of such resins include acrylic gels, urethane gels, silicone gels, urethane resins, and epoxy resins. Among these, urethane gels are preferred. "Gel" generally refers to a high-viscosity dispersion system that has lost its fluidity. It should be noted that the adhesive layer 41 may contain rubber or thermoplastic elastomers in addition to acrylic gels and urethane resins.
[0271] Carbamate resins are resins containing carbamate bonds. Examples of carbamate resins include cured products of ionizing radiation-curable carbamate resin compositions and cured products of thermosetting carbamate resin compositions. Among these, cured products of ionizing radiation-curable carbamate resin compositions are preferred from the viewpoint that they can achieve high hardness, fast curing speed, and excellent mass production capabilities.
[0272] The ionizing radiation-curable urethane resin composition comprises urethane (meth)acrylate, and the thermosetting urethane resin comprises a polyol compound and an isocyanate compound. The urethane (meth)acrylate, polyol compound, and isocyanate compound can be any of monomers, oligomers, and prepolymers.
[0273] The number of (meth)acryloyl groups (functional groups) in urethane (meth)acrylate is preferably 2 or more and 4 or less. When the number of (meth)acryloyl groups in urethane (meth)acrylate is less than 2, the pencil hardness may decrease; conversely, when it exceeds 4, curing shrinkage increases, causing the optical film to curl, and the resin layer may crack during bending. The upper limit of the number of (meth)acryloyl groups in urethane (meth)acrylate is more preferably 3 or less. It should be noted that "(meth)acryloyl group" refers to both "acryloyl group" and "methacryloyl group".
[0274] The weight-average molecular weight of urethane (meth)acrylate is preferably 1500 or more and 20000 or less. When the weight-average molecular weight of urethane (meth)acrylate is less than 1500, its impact resistance may decrease; furthermore, when it exceeds 20000, the viscosity of the ionizing radiation-curable urethane resin composition increases, and its coatability may deteriorate. The lower limit of the weight-average molecular weight of urethane (meth)acrylate is more preferably 2000 or more, and the upper limit is more preferably 15000 or less.
[0275] It should be noted that the resin constituting the adhesive layer 41 is formed from polymer chains (repeating units) of a certain structure, which can be determined, for example, by analyzing the adhesive layer 41 using thermal decomposition GC-MS and FT-IR. In particular, thermal decomposition GC-MS can detect the monomer units contained in the adhesive layer 41 as monomer components, and is therefore useful.
[0276] If the shear storage modulus G' and shear loss modulus G” of the optical thin film having the adhesive layer are within the above range in the frequency region of 25°C and 500Hz to 1000Hz, the adhesive layer 41 may contain ultraviolet absorbers, spectral transmittance modifiers, antifouling agents, inorganic particles and / or organic particles, etc. The ultraviolet absorbers, etc., can be the same substances as those described in the section on functional layer 12, so the description is omitted here.
[0277] (Image display device)
[0278] The aforementioned optical film can be assembled into a foldable image display device. The image display device, facing the viewer, mainly consists of, in sequence, a housing containing a battery, a protective film, a display element, a circular polarizer, a touch sensor, and the optical film. A light-transmitting adhesive layer is disposed between the display element and the circular polarizer, between the circular polarizer and the touch sensor, and between the touch sensor and the optical film, and these components are fixed together by the adhesive layer. It should be noted that the adhesive layer is disposed between the display element and the circular polarizer, between the circular polarizer and the touch sensor, and between the touch sensor and the optical film, but the placement of the adhesive layer is not particularly limited as long as it is between the optical film and the display element.
[0279] The optical thin film can be configured such that the functional layer 12 is positioned closer to the observer than the polyester thin film 11, which serves as the substrate. In an image display device, the functional layer 12 in the optical thin film 10 can constitute the surface of the image display device.
[0280] In another embodiment, a foldable image display device is provided, comprising a display element and an optical film of the present invention disposed closer to the observer than the display element. The optical film of the present invention may be an optical film with an adhesive layer or an optical film without an adhesive layer. In the case of an optical film without an adhesive layer, the display element and the optical film without an adhesive layer may be bonded together via a known adhesive layer or the like.
[0281] In the image display device, the display element is preferably an organic light-emitting diode (OLED) element, including an organic light-emitting diode (OLED). The touch sensor can be positioned closer to the observer than the circular polarizer, or it can be positioned between the display element and the circular polarizer. Furthermore, the touch sensor can be either on-cell or in-cell. For example, OCA (Optical Clear Adhesive) can be used as the adhesive layer.
[0282] According to this embodiment, a polyester film 11 formed of a polyester resin is used as a substrate, and a resin layer A13 is provided between the polyester film 11 as a substrate and the functional layer 12, so that it can be folded and the generation of interference fringes can be suppressed.
[0283] When the back side of the optical film is a polyester film as a substrate, the polyester film as a substrate is in contact with the air layer. Therefore, the reflection at the interface between the polyester film as a substrate and the air layer increases, which may reduce the light transmittance. In particular, when a polyester film formed of a polyester-based resin is used as the substrate polyester film, interface reflection is easily generated because the refractive index of such polyester films is relatively high. In contrast, in this embodiment, a resin layer B15 with a refractive index higher than 1.000 and lower than the refractive index of the polyester film 11 as a substrate is provided on the second surface 11B of the polyester film 11 as a substrate. Therefore, compared with the case where the polyester film as a substrate is in contact with the air layer, interface reflection can be reduced, and the light reflectance can be lowered. As a result, for example, the light transmittance of the optical film with the adhesive layer can be improved.
[0284] Furthermore, when the resin layer B15 contains an antistatic agent, the optical film has a functional layer 12 serving as an antistatic hard coating on the first side 11A of the polyester film 11, which serves as the substrate, and a resin layer B15 containing an antistatic agent on the second side 11B of the polyester film 11, which serves as the substrate. Therefore, it is possible to suppress the adhesion of dust and other contaminants to the optical film. In addition, in this case, even if the protective film is peeled off from the optical film while it is attached to both sides of the optical film, it is possible to suppress the charging of the optical film. This improves the yield rate of the image display device assembly process.
[0285] For optical films used in foldable image display devices, their surfaces are sometimes subjected to impacts, thus requiring impact resistance. When an impact is applied to the surface of the optical film, it can sometimes dent. Furthermore, components located further inside the image display device than the optical film, such as the display panel (e.g., an organic light-emitting diode panel), can sometimes be damaged. Regarding dents on the surface of the optical film, there are dents caused by the optical film itself and dents caused by flexible layers, such as adhesive layers located further inside the image display device than the optical film. "Dents caused by the optical film itself" refers to dents caused by the deformation of the optical film itself due to an impact on its surface. "Dents caused by flexible layers" refers to dents caused by the plastic deformation of the flexible layer located further inside the image display device than the optical film when an impact is applied, resulting in the optical film following the plastic deformation of the flexible layer. Therefore, currently, in optical thin films, it is preferable to suppress indentations caused by the optical thin film itself and by the flexible layer when an impact is applied to the surface of the optical thin film, and to obtain excellent impact resistance such that components located further inside the image display device than the optical thin film are not damaged. Here, the shear loss tangent tanδ is conventionally known as an indicator of impact absorption performance. Therefore, it is also considered to use the shear loss tangent tanδ to represent the impact resistance of an optical thin film with a functional layer on the first side and a resin layer on the second side of a polyester thin film as a substrate. However, for the shear loss tangent tanδ, when an impact is applied to the surface of the optical thin film (the surface of the functional layer), it is not possible to suppress indentations on the surface of the optical thin film caused by the optical thin film itself and by the flexible layer, as well as damage to components located further inside the image display device than the optical thin film. This is believed to be because the shear loss tangent tanδ is the ratio of the shear loss modulus G” to the shear storage modulus G’ (G” / G’). The inventors conducted further in-depth research and found that, in order to suppress surface depressions caused by the optical film itself and by the soft layer when an impact is applied to the surface of the optical film, as well as damage to components located further inside the image display device than the optical film, it is important to balance the film thickness of the resin layer, the shear storage modulus G', and the shear loss modulus G".
[0286] Such features can be derived by the fact that the resin layer in this invention is a cured layer of a cured resin composition formed from a composition comprising polycarbonate polyurethane resin, polyester resin, end-capped isocyanate crosslinking agent and particles, and the polyester resin has a fused polycyclic aromatic structure.
[0287] According to this embodiment, in an optical film having a functional layer 12 on the first surface 11A of a polyester film 11 as a substrate and an adhesive layer 41 on the second surface 11B, the adhesive layer 41 has a thickness of 25 μm or more and 300 μm or less, the shear storage modulus G' of the optical film is more than 200 MPa and less than 1200 MPa, and the shear loss modulus G” of the optical film is more than 3 MPa and less than 150 MPa. Therefore, it is foldable, and when an impact is applied to the surface of the optical film, it can suppress surface depressions caused by the optical film itself and surface depressions caused by a flexible layer located further inside the image display device than the optical film, and can suppress damage to components such as display elements located inside the image display device. As a result, excellent impact resistance can be obtained.
[0288] Example
[0289] To illustrate the invention in detail, the following examples are provided, but the invention is not limited to these descriptions. It should be noted that the "100% solid content conversion value" mentioned below refers to the value when the solid content in the solvent diluent is set to 100%.
[0290] <Refractive index>
[0291] The refractive indices of the functional layer and various resin layers are determined as follows: The functional layer composition and the resin layer composition are coated on a 50 μm thick PET without easy bonding treatment to form a cured film with a thickness of 1 to 10 μm. To prevent back reflection, a black vinyl tape (e.g., Yamato Vinyl Tape NO200-38-21 (38 mm width)) with a width greater than the area of the light spot to be measured is attached to the side (back side) of the PET that is not coated with the functional layer composition and the resin layer composition. The average reflectance at wavelengths of 380 to 780 nm is measured using a spectrophotometer (product name "UV-2450", manufactured by Shimadzu Corporation). The obtained average reflectance is used to determine the refractive index based on the above formula (2).
[0292] <Film thickness>
[0293] Regarding the film thickness of each layer, a scanning transmission electron microscope (STEM) (product name "S-4800", manufactured by Hitachi High Technology Co., Ltd.) was used to photograph the cross-section of the optical thin film. The film thickness of each layer was measured at 20 points in the cross-sectional image, and the arithmetic mean of these 20 thicknesses was taken. The cross-sectional photographs of the optical thin film were taken as follows: First, a block containing 1mm × 10mm pieces of optical thin film embedded in embedding resin was prepared. Uniform slices without pores and with a thickness of 70nm or more and 100nm or less were cut from this block using standard slicing methods. Slices were prepared using an "EM UC7 ultramicrotome" (Leica Microsystems Co., Ltd.). Then, these uniform slices without pores were used as the measurement sample. A cross-sectional photograph of the measurement sample was then taken using a scanning transmission electron microscope (STEM). During the photographing of this cross-sectional image, the detector was set to "TE", the accelerating voltage was set to "30kV", and the emission current was set to "10μA" for STEM observation. Regarding magnification, while observing whether the different layers could be distinguished, the focus was adjusted, and the contrast and brightness were adjusted appropriately between 5000x and 200,000x. It should be noted that when shooting cross-sectional photos, the aperture was also set to "beam monitor stop 3", the objective lens stop was set to "3", and WD was set to "8mm".
[0294] <Evaluation of Interference Fringes>
[0295] In the optical films of the embodiments and comparative examples, the observation of interference fringes was evaluated. Specifically, a black acrylic sheet to prevent back reflection was adhered to the back of the optical film via a transparent adhesive. Light was shone onto each optical film from the surface side, and interference fringes were visually observed. A three-wavelength fluorescent lamp was used as the light source. The generation of interference fringes was evaluated according to the following criteria.
[0296] 〇: No interference fringes detected.
[0297] △: Several interference fringes were detected, but the level is sufficient for practical use.
[0298] ×: Interference fringes were clearly identified.
[0299] <Continuous foldability and sealing of the optical film before durability testing>
[0300] The optical thin film was cut into 30mm × 100mm rectangles to create a sample. For this sample, the shorter side (30mm) was fixed to a durability testing machine (product name "DLDMLH-FS", manufactured by YUASA SYSTEM Co., Ltd.) using a fixing device. Figure 2As shown in (B), the sample was installed with a minimum interval of 10 mm between the two opposite edges. A continuous folding test was conducted 10,000 times, folding the sample surface side 180° (with the hard coating on the inside and the substrate, resin layer B, or adhesive layer on the outside). The presence of any lifting (gap) between the substrate and the functional layer was investigated, as well as any cracking or breakage at the bends. The results of the continuous folding test were categorized into continuous folding and sealing performance, and evaluated according to the following criteria. It should be noted that the sample used in the continuous folding test was cut from the optical film prior to the durability test described later.
[0301] (Continuous folding)
[0302] 〇: No cracks or breaks occurred at the bending point during the continuous folding test.
[0303] △: In the continuous folding test, some cracks or breaks occurred at the bending point, but the level is not a problem for actual use.
[0304] ×: In the continuous folding test, obvious cracks or breaks occurred at the bending point.
[0305] (Seamless fit)
[0306] 〇: No lifting occurred between the substrate and the hard coating during the continuous folding test.
[0307] △: In the continuous folding test, some lifting occurred between the substrate and the hard coating, but it was at a level that would not cause problems in actual use.
[0308] ×: In the continuous folding test, a noticeable lift-up occurred between the substrate and the hard coating.
[0309] <Continuous foldability and sealing of the optical film after durability testing>
[0310] A durability test was conducted by placing the optical film at 60°C and 90% relative humidity for 12 hours. The optical film after the durability test was cut into 30mm × 100mm rectangles to create samples. For each sample, the short side (30mm) was fixed to a durability testing machine (product name "DLDMLH-FS", manufactured by YUASA SYSTEM Co., Ltd.) using a fixing device. Figure 2As shown in (B), the sample was installed with a minimum interval of 10 mm between the two opposite edges. A continuous folding test was conducted 10,000 times, folding the sample surface side 180° (with the functional layer on the inside and the substrate, resin layer B, or adhesive layer on the outside). The presence of any lifting (gap) between the substrate and the functional layer was investigated, as well as any cracking or breakage at the bends. The results of the continuous folding test were categorized into continuous folding and fit, and evaluated according to the following criteria.
[0311] (Continuous folding)
[0312] 〇: No cracks or breaks occurred at the bending point during the continuous folding test.
[0313] △: In the continuous folding test, some cracks or breaks occurred at the bending point, but the level is not a problem for actual use.
[0314] ×: In the continuous folding test, obvious cracks or breaks occurred at the bending point.
[0315] (Seamless fit)
[0316] 〇: No lifting occurred between the substrate and the hard coating during the continuous folding test.
[0317] △: In the continuous folding test, some lifting occurred between the substrate and the hard coating, but it was at a level that would not cause problems in actual use.
[0318] ×: In the continuous folding test, a noticeable lift-up occurred between the substrate and the hard coating.
[0319] <Pencil Hardness>
[0320] The pencil hardness of the surface of optical thin films was determined based on JIS K5600-5-4:1999. The pencil hardness test was conducted as follows: Optical thin films cut to 30mm × 100mm were fixed to a glass plate without bending or wrinkling using a Cellotte (registered trademark) manufactured by NICHIBANCo., Ltd. The surface of the optical thin film was tested using a pencil hardness testing machine (product name "Pencil Scratch Coating Hardness Tester (Electric Type)", manufactured by Toyo Seiki Co., Ltd.) while applying a 750g load to a pencil (product name "Uni", manufactured by Mitsubishi Pencil Co., Ltd.) and moving the pencil at a speed of 1mm / second. The pencil hardness was defined as the highest hardness that would not cause damage to the surface of the optical thin film during the pencil hardness test. It should be noted that, in determining the pencil hardness, multiple pencils of different hardness were used. Each pencil underwent five pencil hardness tests. If no damage was visually detected on the surface of the optical film when viewed under fluorescent light in four or more of the five tests, the pencil of that hardness was considered not to have caused damage to the surface of the optical film. It should also be noted that the optical film used was the one before the aforementioned durability tests were conducted.
[0321] <Peel resistance and electrical conductivity>
[0322] A protective film was attached to the surface of an optical thin film, and the peel charge was measured when the protective film was peeled off the surface of the optical thin film to evaluate the magnitude of the peel charge. Specifically, a protective film with an adhesive layer (product name "SAT2038T-JSL", manufactured by Sun A Kaken Co., Ltd.) was attached to the surface of the optical thin film. Under conditions of 23°C and 50% relative humidity, the protective film was peeled off 180° from the surface of the optical thin film at a peeling speed of 300 mm / min. The surface potential of the optical thin film at this point was measured at a distance of 50 mm using an electrostatic meter (product name "KSD-0103", manufactured by Kasuga Electric Co., Ltd.), and the peel charge was thus measured. The peel charge was calculated as the arithmetic mean of the peel charges obtained from 10 measurements on the surface of the optical thin film. The evaluation criteria are as follows. It should be noted that the optical thin film used was the one before the above durability test.
[0323] ○: The stripping charge on the surface of the optical thin film is in the range of -10kV to 10kV.
[0324] ×: The stripping charge on the surface of the optical thin film exceeds ±10kV.
[0325] <Yellow Index (YI)>
[0326] The yellow index of the optical film was measured. Specifically, firstly, an optical film cut to a size of 50mm × 50mm was placed in a spectrophotometer (product name "UV-2450", manufactured by Shimadzu Corporation, light source: tungsten lamp and deuterium lamp) with the substrate side of the optical film as the light source side. The optical film was free of defects (foreign matter contamination), cracks, wrinkles, and stains, and was held in a flat state without curling in the spectrophotometer. In this state, under the following measurement conditions, the transmittance was measured at the lowest 5 points within 1nm before and after the wavelength from 300nm to 780nm, and the average value was calculated to obtain the yellow index. Then, the above transmittance measurement data was read on the monitor connected to the UV-2450, and "YI" was checked in the calculation items to obtain YI. It should be noted that the optical film used was the one before the above durability test.
[0327] (Measurement conditions)
[0328] Wavelength range: 300nm~780nm
[0329] • Scanning speed: High speed
[0330] • Slit width: 2.0
[0331] • Sampling interval: Automatic (0.5nm interval)
[0332] Lighting: C
[0333] • Light source: D2 and WI
[0334] • Field of view: 2°
[0335] • Light source switching wavelength: 360nm
[0336] • S / R switching: Standard
[0337] • Detector: PM
[0338] • Automatic zeroing: Performed at 550nm after baseline scan
[0339] <Total transmittance measurement>
[0340] For optical films, a haze meter (product name "HM-150", manufactured by Murakami Color Research Laboratory Co., Ltd.) is used to measure the total light transmittance in accordance with JIS K7361-1:1997. The aforementioned total light transmittance is a value obtained by cutting an optical film into a size of 50 mm × 100 mm, arranging the film in a state free from curls, wrinkles, fingerprints, dust and the like such that the hard coat side faces the non-light source side, performing measurement 3 times on one optical film, and taking the arithmetic mean of the 3 measured values. It should be noted that an optical film before the above durability test is used as the optical film.
[0341] <Measurement of G', G", and tanδ>
[0342] The shear storage modulus G', shear loss modulus G”, and shear loss tangent tanδ of the optical thin film were measured. Specifically, the optical thin film was first punched into a rectangular shape of 10mm × 5mm to form a sample. Then, two of these samples were prepared and mounted on the measuring fixture of a dynamic viscoelasticity measuring device (product name "Rheogel-E4000", manufactured by UBM). Specifically, the solid shear fixture has a 1mm thick metal solid shear plate and two L-shaped metal parts disposed on both sides of the solid shear plate. One sample is clamped between the solid shear plate and the L-shaped metal parts, and the other sample is clamped by the solid shear plate and the other L-shaped metal part. In this case, the sample is clamped with the resin layer on the solid shear plate side and the hard coating on the L-shaped metal part side. Then, the L-shaped metal parts were fastened together with screws to secure the sample. Next, a tensile testing chuck consisting of an upper and lower chuck was installed on the dynamic viscoelasticity measuring device (product name "Rheogel-E4000", manufactured by UBM). A solid shear fixture was then placed between the upper and lower chucks with a chuck spacing of 20 mm. The set temperature was then set to 25°C and increased at a rate of 2°C / min. Under these conditions, while the solid shear plate was fixed, longitudinal vibration with a strain of 1% and a frequency between 500 Hz and 1000 Hz was applied to the two L-shaped metal parts. Simultaneously, the dynamic viscoelasticity of the solid was measured at 25°C, and the shear storage modulus G', shear loss modulus G" and shear loss tangent tanδ of the optical thin film were measured. Here, the shear storage modulus G', shear loss modulus G”, and shear loss tangent tanδ in the frequency region above 500Hz and below 1000Hz of the optical thin film are as follows: Longitudinal vibrations at frequencies of 500Hz, 750Hz, and 950Hz are applied to the L-shaped metal part, and the shear storage modulus G', shear loss modulus G”, and shear loss tangent tanδ of the optical thin film are measured at each frequency. The arithmetic mean of these shear storage modulus G', shear loss modulus G”, and shear loss tangent tanδ is calculated. This measurement is repeated three times, and the three arithmetic mean values are further arithmetically averaged to obtain the final value. It should be noted that the optical thin film used is the one before the aforementioned durability test.
[0343] Impact Resistance Test
[0344] The optical film was placed directly on the surface of a 0.7 mm thick soda glass with the soda glass side becoming the resin layer side. Three impact resistance tests were conducted, each involving dropping a 100 g, 30 mm diameter iron ball from a height of 30 cm onto the surface of the functional layer of the optical film.
[0345] In addition, the optical film was placed on a 0.7 mm thick soda glass substrate with the soda glass side as the adhesive layer side, separated by a 200 μm thick adhesive sheet (product name "High Transparency Double-Sided Adhesive Tape 8146-2", manufactured by 3M). Impact resistance test B was performed three times, in which a 100 g, 30 mm diameter iron ball was dropped from a height of 30 cm onto the surface of the hard coating of the optical film. It should be noted that the drop position of the iron ball was changed each time in impact resistance tests A and B. Then, in the optical film after impact resistance test A, the surface of the functional layer was visually evaluated for dents, and the soda glass was evaluated for cracks. Similarly, in the optical film after impact resistance test B, the surface of the functional layer was visually evaluated for dents.
[0346] (Evaluation of depressions on hard-coated surfaces)
[0347] ○: No depressions were detected on the surface of the hard coating in both cases of viewing it from the front and from an angle.
[0348] △: No depressions were observed on the surface of the hard coating when viewed from the front, but depressions were confirmed on the surface of the hard coating when viewed from an oblique angle.
[0349] ×: In both cases of viewing the hard coating from the front and from an angle, obvious depressions were observed on the surface of the hard coating.
[0350] (Evaluation of breakage of soda glass)
[0351] 〇: The sodium glass is not broken.
[0352] △: The soda glass is damaged but not broken.
[0353] ×: The soda glass cracked in all three tests.
[0354] [Polycarbonate polyurethane resin]
[0355] Synthesis of polycarbonate polyurethane resin (PCPU-1):
[0356] 29.4 parts by mass of dicyclohexylmethane-4,4'-diisocyanate, 63.6 parts by mass of polycarbonate diol with a melting point of 33°C and using 1,5-pentanediol / 1,6-hexanediol (molar ratio = 45 / 55) as the main raw materials (number average molecular weight 1000), 7 parts by mass of dimethylolpropionic acid, and 200 parts by mass of methyl ethyl ketone as solvent were added to a four-necked flask equipped with a stirrer, a serpentine condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer. The mixture was stirred at 75°C for 3 hours under a nitrogen atmosphere. The infrared spectrum of the reaction solution was measured to confirm the disappearance of isocyanate groups in the reaction solution. Next, the solution was cooled to room temperature, and 8.2 parts by mass of triethylamine were added to obtain a polycarbonate polyurethane resin (PCPU-1) solution with a solid content of 50.0% by mass.
[0357] Preparation of an aqueous dispersion of polycarbonate polyurethane resin (PCPU-1) (PCPU-1WD):
[0358] Add the specified amount of water to the reaction vessel equipped with a high-speed homogenizer, adjust the temperature to 25°C, and stir at a speed of 2000 min. -1 The polycarbonate polyurethane resin (PCPU-1) solution was slowly added while stirring and mixing to achieve aqueous dispersion. Then, methyl ethyl ketone, used as a solvent, was removed under reduced pressure. The concentration was adjusted by water to prepare an aqueous dispersion (PCPU-1WD) of polycarbonate polyurethane resin (PCPU-1) with a solid content of 35.0% by mass.
[0359] <Specific viscosity of polyester resin ηsp / c (unit: dl / g)>
[0360] 0.10 g of polyester resin was dissolved in 25 ml of a mixed solvent of phenol / tetrachloroethane (mass ratio 6 / 4), and the viscosity was measured using an Ubbelohde viscometer at 30 °C.
[0361] <Resin Composition of Polyester>
[0362] Polyester resin was dissolved in deuterated chloroform, and the analysis was performed using a Varian GEMINI-200 nuclear magnetic resonance (NMR) analyzer. 1 H-NMR analysis was used to determine the mole percentage of each component based on its integral ratio.
[0363] <Viscosity of polyester resin dispersion>
[0364] Add the aqueous dispersion of polyester resin to a 140cc glass bottle, and measure the viscosity of the aqueous dispersion using a ModelBL (TOKIMEC INC.) viscometer with a rotor of 60 rpm for 1 minute in a constant temperature bath at 25°C.
[0365] [Polyester resin]
[0366] Manufacturing of polyester resin (PEs-1):
[0367] Polyester resin (PEs-1) was polymerized according to a known polymerization method. The composition of the resulting polymer was then analyzed. 1 ¹H-NMR analysis was performed, and the molar percentage of each component was determined by its integral ratio. The results are recorded in Table 4. The specific viscosity of the obtained polyester resin was 0.493 dl / g.
[0368] The following describes the abbreviations recorded in Table 4.
[0369] TPA: Terephthalic acid
[0370] IPA: Isophthalic acid
[0371] NDC: Naphthalene dicarboxylic acid
[0372] SA: Sebacic acid
[0373] DSS: Sodium dimethyl isophthalate-5-sulfonate
[0374] EG: Ethylene glycol
[0375] HD: Hexanediol
[0376] DEG: Diethylene glycol
[0377] NPG: Neopentyl Glycol
[0378] Preparation of polyester aqueous dispersion (PEs-1WD):
[0379] In a reactor equipped with a stirrer, thermometer, and reflux device, 30 parts by weight of copolyester resin (PEs-1) and 15 parts by weight of ethylene glycol-n-butyl ether were added. The mixture was heated and stirred at 110°C to dissolve the resin. After the resin was completely dissolved, 55 parts by weight of water were slowly added to the polyester solution while stirring. After the water was added, the liquid was cooled to room temperature while stirring to prepare a milky white aqueous dispersion of polyester resin (PEs-1) (PEs-1WD) with a solid content of 25.1% by weight. The viscosity of the obtained aqueous dispersion was 32 mPa·s.
[0380] [Cross-linking agent]
[0381] Preparation of an aqueous dispersion (C-1WD) of a capped isocyanate-based crosslinking agent (C-1):
[0382] In a flask equipped with a stirrer, thermometer, and reflux condenser, 125.2 parts by weight of a polyisocyanate compound with a biuret structure (manufactured by Asahi Kasei Chemicals, DURANATE 24A-100, NCO concentration 23.1%), based on hexamethylene diisocyanate, 50.0 parts by weight of dipropylene glycol dimethyl ether, and 68.8 parts by weight of 3,5-dimethylpyrazole were added. The mixture was stirred at 70°C under a nitrogen atmosphere for 2 hours. The infrared spectrum of the reaction solution was then measured to confirm the disappearance of the isocyanate group absorption. Next, after cooling to room temperature, 6 parts by weight of polyethylene glycol (n=12) monolaurate were added, and the mixture was stirred at 2000 min... -1 Water was added while stirring and mixing. The concentration was adjusted by water to prepare an aqueous dispersion (C-1WD) of 30.0% by mass of the end-capped isocyanate crosslinking agent (C-1).
[0383] <Average particle size>
[0384] [Method using scanning electron microscopy]
[0385] The average particle size of the particles present in the resin layer of this invention can be determined by the following method: The particles are photographed using a scanning electron microscope (SEM), and the maximum diameter (distance between the two furthest points) of 300 to 500 particles is measured at a magnification of 2 to 5 mm for the smallest particle size. The arithmetic mean of these particles is taken as the average particle size.
[0386] Dynamic light scattering method
[0387] The average particle size can also be determined during the manufacturing of particles or films using dynamic light scattering. The sol is diluted with a dispersion medium, and the parameters of the dispersion medium are measured using a submicron particle analyzer N4 PLUS (Beckman Coulter). The average particle size is calculated using the cumulative moment method. The average particle size in the sol is then observed using dynamic light scattering; if particle aggregation is present, the average particle size of these aggregated particles is also observed.
[0388] <Refractive index of particles>
[0389] The refractive index of the particles can be determined by the following method. Inorganic particles are dried at 150°C, pulverized in a mortar, and then immersed in solvent 1 (a solvent with a lower refractive index than the particles). Solvent 2 (a substance with a higher refractive index than the particles) is then added in small, incremental amounts until the particles become approximately transparent. The refractive index of the liquid is measured using an Abbe refractometer (Abbe refractometer manufactured by Atago Co., Ltd.). The measurement is performed at 23°C under D-rays (wavelength 589 nm). Solvent 1 and solvent 2 are selected to be miscible solvents. Examples of solvents that can be used, depending on the refractive index, include 1,1,1,3,3,3-hexafluoro-2-propanol, 2-propanol, chloroform, carbon tetrachloride, toluene, and glycerol.
[0390] (Zirconium oxide particles)
[0391] 2283.6 g of pure water and 403.4 g of oxalic acid dihydrate were added to a 3-liter glass container and heated to 40°C to prepare a 10.72% by mass oxalic acid aqueous solution. While stirring the aqueous solution, 495.8 g of zirconium oxycarbonate powder (ZrOCO3, manufactured by AMR International Corp., equivalent to ZrO2, containing 39.76% by mass) was slowly added. After mixing for 30 minutes, the mixture was heated at 90°C for 30 minutes. Then, 1747.2 g of a 25.0% by mass tetramethylammonium hydroxide aqueous solution (manufactured by Tama Chemical Industry Co., Ltd.) was slowly added over 1 hour. At this point, the mixture was in slurry form, containing 4.0% by mass of ZrO2. The slurry was transferred to a stainless steel autoclave and hydrothermally treated at 145°C for 5 hours. The product after hydrothermal treatment was free of undissolved matter and completely gelled. The obtained sol contained 4.0% by mass ZrO2, had a pH of 6.8, and an average particle size of 19 nm based on dynamic light scattering. Furthermore, the transmittance was measured to be 88% when the sol was adjusted to a ZrO2 concentration of 2.0% by mass with pure water. Particle observation using a transmission electron microscope revealed aggregated ZrO2 particles of approximately 7 nm in size. Using an ultrafiltration device, 4000 g of the 4.0% by mass ZrO2 sol obtained through hydrothermal treatment was washed and concentrated with the slow addition of pure water, yielding 953 g of a 13.1% by mass ZrO2 sol with a transmittance of 76% at a pH of 4.9. The refractive index of the obtained zirconia-based microparticles was 1.75.
[0392] (Zirconium oxide sol)
[0393] 300g of a zirconia sol with a ZrO2 concentration of 13.1% by mass, obtained through the above washing and concentration process, was further concentrated by adding 3.93g of a 20% by mass citric acid aqueous solution and 11.0g of a 25% by mass tetramethylammonium hydroxide aqueous solution to 300g of zirconia sol using an ultrafiltration device. This yielded 129g of a high-concentration zirconia sol with a ZrO2 concentration of 30.5% by mass. The resulting high-concentration zirconia sol had a pH of 9.3 and an average particle size of 19nm based on dynamic light scattering. Furthermore, this zirconia sol exhibited no precipitate and remained stable for more than one month at 50°C.
[0394] <Composition 1 for Resin Layer A>
[0395] Prepare a coating solution with the following composition.
[0396] 42.38 parts by weight of water
[0397] 29.79 parts by weight of isopropanol
[0398] 4.50 parts by weight of zirconium oxide sol
[0399] (Zirconium oxide sol with an average particle size of 20 nm and a solid content concentration of 30% by mass)
[0400] 0.87 parts by weight of silica sol
[0401] (Silica sol with an average particle size of 450 nm and a solid content concentration of 4% by mass)
[0402] PCPU-1WD 5.62 parts by weight
[0403] (Solid component concentration 35.0% by mass)
[0404] PEs-1WD 11.08 parts by weight
[0405] (Solid component concentration 25.1% by mass)
[0406] C-1WD 5.20 parts by weight
[0407] (Solid component concentration 30.0% by mass)
[0408] 0.30 parts by weight of surfactant
[0409] (Organosilicon-based, solid content concentration 10.0% by mass)
[0410] 0.26 parts by weight of high-boiling-point solvent
[0411] <Composition 2 for Resin Layer A>
[0412] Prepare a coating solution with the following composition.
[0413] 40.30 parts by weight of water
[0414] 29.79 parts by weight of isopropanol
[0415] 4.50 parts by weight of zirconium oxide sol
[0416] (Zirconium oxide sol with an average particle size of 20 nm and a solid content concentration of 30% by mass)
[0417] 0.87 parts by weight of silica sol
[0418] (Silica sol with an average particle size of 450 nm and a solid content concentration of 4% by mass)
[0419] PCPU-1WD 1.31 parts by weight
[0420] (Solid component concentration 35.0% by mass)
[0421] PEs-1WD 17.46 parts by weight
[0422] (Solid component concentration 25.1% by mass)
[0423] C-1WD 5.20 parts by weight
[0424] (Solid component concentration 30.0% by mass)
[0425] 0.30 parts by weight of surfactant
[0426] (Organosilicon-based, solid content concentration 10.0% by mass)
[0427] 0.26 parts by weight of high-boiling-point solvent
[0428] <Composition 1 for Resin Layer B>
[0429] Prepare a coating solution with the following composition.
[0430] 52.75 parts by weight of water
[0431] 30.95 parts by weight of isopropanol
[0432] 2.60 parts by weight of zirconium oxide sol
[0433] (Zirconium oxide sol with an average particle size of 20 nm and a solid content concentration of 30% by mass)
[0434] 0.50 parts by weight of silica sol
[0435] (Silica sol with an average particle size of 450 nm and a solid content concentration of 4% by mass)
[0436] PCPU-1WD 3.25 parts by weight
[0437] (Solid component concentration 35.0% by mass)
[0438] PEs-1WD 6.40 parts by weight
[0439] (Solid component concentration 25.1% by mass)
[0440] C-1WD 3.00 parts by weight
[0441] (Solid component concentration 30.0% by mass)
[0442] 0.30 parts by weight of surfactant
[0443] (Organosilicon-based, solid content concentration 10.0% by mass)
[0444] 0.26 parts by weight of high-boiling-point solvent
[0445] <Composition 2 for Resin Layer B>
[0446] Prepare a coating solution with the following composition.
[0447] 51.56 parts by weight of water
[0448] 30.95 parts by weight of isopropanol
[0449] 2.60 parts by weight of zirconium oxide sol
[0450] (Zirconium oxide sol with an average particle size of 20 nm and a solid content concentration of 30% by mass)
[0451] 0.50 parts by weight of silica sol
[0452] (Silica sol with an average particle size of 450 nm and a solid content concentration of 4% by mass)
[0453] PCPU-1WD 0.76 parts by weight
[0454] (Solid component concentration 35.0% by mass)
[0455] PEs-1WD 10.08 parts by weight
[0456] (Solid component concentration 25.1% by mass)
[0457] C-1WD 3.00 parts by weight
[0458] (Solid component concentration 30.0% by mass)
[0459] 0.30 parts by weight of surfactant
[0460] (Organosilicon-based, solid content concentration 10.0% by mass)
[0461] 0.26 parts by weight of high-boiling-point solvent
[0462] <Composition 1 for Functional Layer>
[0463] Prepare a coating solution with the following composition.
[0464] 21.00 parts by weight of isopropanol
[0465] 49.00 parts by weight of toluene
[0466] Pentaerythritol triacrylate 21.38 parts by weight
[0467] (Shinnakamura Chemical Manufacturing A-TMM-3)
[0468] 7.12 parts by weight of urethane acrylate
[0469] (Mitsubishi Chemical Corporation UV-7600B)
[0470] 1.50 parts by weight of photopolymerization initiator
[0471] (IGM Resins BV Omnirad184)
[0472] <Composition 2 for Functional Layer>
[0473] Prepare a coating solution with the following composition.
[0474] 64.40 parts by weight of methyl ethyl ketone
[0475] 27.20 parts by weight of dipentaerythritol hexaacrylate
[0476] (Niinakamura Chemicals A-DPH)
[0477] 3.40 parts by weight of polyethylene glycol diacrylate
[0478] (Kyoei Chemical Manufacturing Co., Ltd. Light Acrylate 9EG-A)
[0479] 4.00 parts by weight of bisphenol A diacrylate
[0480] (Kyoei Chemical Manufacturing Light Acrylate BP-4PA)
[0481] 1.00 parts by weight of photopolymerization initiator
[0482] (IGM Resins BV Omnirad184)
[0483] <Compositions for Adhesive Layers>
[0484] Prepare a coating solution with the following composition.
[0485] 10.00 parts by weight of methyl isobutyl ketone
[0486] 72.25 parts by weight of urethane acrylate
[0487] (UV3310B manufactured by Japan Synthetic Chemicals)
[0488] 12.75 parts by weight of phenoxyethyl acrylate
[0489] (Viscoat #192, manufactured by Osaka Organic Chemical Industry)
[0490] 5.00 parts by weight of photopolymerization initiator
[0491] (IGM Resins BV Omnirad184)
[0492] <Example 1>
[0493] As a polyester film serving as the substrate, a polyester substrate with a refractive index of 1.650 and a thickness of 50 μm is prepared. Resin layer A composition 1 is applied to one side of the polyester substrate using a bar coater to form a coating film. Then, the formed coating film is heated at 90°C for 1 minute to evaporate the solvent, and then heated at 230°C for 1 minute to cure the coating film, forming a resin layer A-1 with a refractive index of 1.57 and a film thickness of 100 nm. Functional layer composition 1 is then applied to the surface of resin layer A-1 using a bar coater to form a coating film. Then, the formed coating film is heated at 70°C for 1 minute to evaporate the solvent, and then irradiated in air using an ultraviolet light irradiation device (Fusion UV Systems Japan, light source H bulb) with a cumulative light intensity of 200 mJ / cm². 2 The coating is cured by irradiating it with ultraviolet light to form a functional layer-1 with a refractive index of 1.52 and a film thickness of 5 μm. Next, a resin layer B composition 1 is applied to the second surface of the polyester substrate, opposite to the functional layer-1, using a bar coater to form a coating film. Then, the formed coating film is heated at 90°C for 1 minute to evaporate the solvent, and then heated at 230°C for 1 minute to cure the coating film, forming a resin layer B-1 with a refractive index of 1.57 and a film thickness of 50 nm. Next, an adhesive layer composition is applied to the surface of the resin layer B-1 using a bar coater to form a coating film. Then, the formed coating film is heated at 70°C for 1 minute to evaporate the solvent, and then irradiated with ultraviolet light (FusionUV Systems Japan, light source H bulb) in air at a cumulative light intensity of 1200 mJ / cm². 2The coating was cured by irradiating it with ultraviolet light, forming a resin layer of urethane-based resin with a refractive index of 1.50 and a thickness of 50 μm. An optical film was then fabricated with resin layer A adjacent to the functional layer and resin layer B adjacent to the adhesive layer, separated by a polyester film as a substrate. The various evaluation results of the obtained optical films are recorded in Tables 2 and 3.
[0494] <Example 2, Example 3, Comparative Example 2>
[0495] Except that the thickness of the formed resin layer A was changed to the thickness described in Table 1, the optical thin film was fabricated in the same manner as in Example 1. The various evaluation results of the obtained optical thin film are described in Tables 2 and 3.
[0496] <Example 4>
[0497] Except that the thickness of the formed resin layer B was changed to the thickness described in Table 1, the optical thin film was fabricated in the same manner as in Example 1. The various evaluation results of the obtained optical thin film are described in Tables 2 and 3.
[0498] <Example 5>
[0499] The formed resin layer B was removed, and an adhesive layer was directly formed on the second surface of the polyester substrate. Otherwise, the optical film was fabricated in the same manner as in Example 1. The various evaluation results of the obtained optical films are recorded in Tables 2 and 3.
[0500] <Example 6>
[0501] Before forming resin layer A-1, composition 2 for resin layer A is applied to the first side of a polyester substrate in an adjacent manner using a bar coater to form a coating film. Then, the formed coating film is heated at 90°C for 1 minute to evaporate the solvent, and then heated at 230°C for 1 minute to cure the coating film, forming resin layer C with a refractive index of 1.60 and a thickness of 100 nm. Resin layer A-1 is formed on the surface of resin layer C in the same manner as in Example 1. Subsequently, an optical thin film is prepared in the same manner as in Example 1. Various evaluation results of the obtained optical thin films are described in Tables 2 and 3.
[0502] <Example 7>
[0503] Composition 2 was used instead of composition 1 for resin layer A, and resin layer A-2 was formed instead of resin layer A-1 in the same manner as in Example 1. Otherwise, the optical film was fabricated in the same manner as in Example 1. Various evaluation results of the obtained optical films are described in Tables 2 and 3.
[0504] <Example 8>
[0505] Resin layer B was prepared by using composition 2 instead of composition 1, and resin layer B-2 was formed instead of resin layer B-1 in the same manner as in Example 1. Otherwise, the optical film was prepared in the same manner as in Example 1. The various evaluation results of the obtained optical film are described in Tables 2 and 3.
[0506] <Example 9, Example 10>
[0507] Except for changing the thickness of the functional layer to the film thickness described in Table 1, the optical thin film was fabricated in the same manner as in Example 1. The various evaluation results of the obtained optical thin film are described in Tables 2 and 3.
[0508] <Example 11, Example 12>
[0509] Except that the thickness of the adhesive layer was changed to the film thickness described in Table 1, the optical thin film was fabricated in the same manner as in Example 1. The various evaluation results of the obtained optical thin film are described in Tables 2 and 3.
[0510] <Example 13>
[0511] Using functional layer composition 2 instead of functional layer composition 1, and adjusting the film thickness to the values in Table 1, functional layer 2 was formed in place of functional layer 1 using the same method as in Example 1. Otherwise, the optical thin film was fabricated in the same manner as in Example 1. Various evaluation results of the obtained optical thin films are recorded in Tables 2 and 3.
[0512] <Example 14>
[0513] Composition 2 was used instead of composition 1 for resin layer A, and resin layer A-2 was formed instead of resin layer A-1 using the same method as in Example 13. Otherwise, the optical film was fabricated in the same manner as in Example 13. Various evaluation results of the obtained optical films are recorded in Tables 2 and 3.
[0514] <Comparative Example 1>
[0515] Without forming resin layer A, a functional layer is directly formed on the first surface of a polyester substrate, and without forming resin layer B, an adhesive layer is directly formed on the second surface of the polyester substrate. Otherwise, the optical film is fabricated in the same manner as in Example 1. Various evaluation results of the obtained optical films are recorded in Tables 2 and 3.
[0516] <Comparative Example 3>
[0517] Without forming resin layer A, a functional layer is directly formed on the first surface of a polyester substrate. Otherwise, the optical film is fabricated in the same manner as in Example 1. The various evaluation results of the obtained optical films are recorded in Tables 2 and 3.
[0518] <Comparative Example 4>
[0519] The thickness of resin layer B was set to 350 nm, and the optical thin film was fabricated in the same manner as in Example 1. The various evaluation results of the obtained optical thin film are recorded in Tables 2 and 3.
[0520] [Table 1]
[0521]
[0522] [Table 2]
[0523]
[0524] [Table 3]
[0525]
[0526] [Table 4]
[0527]
[0528] Industrial availability
[0529] The optical thin film of this invention is suitable for use as a foldable optical thin film, exhibiting high bonding reliability between the functional layer and the substrate, and excellent optical interference properties. Furthermore, it also demonstrates excellent reliability as an image display device, enabling its wide application in optical applications and other related fields.
[0530] Explanation of reference numerals in the attached figures
[0531] 10 Optical Thin Films
[0532] 11 Polyester film
[0533] The first surface of the 11A substrate
[0534] The second side of the 11B substrate
[0535] 12 Functional Layer
[0536] 13 Resin layer A
[0537] 14 Resin layer C
[0538] 15 Resin layer B
[0539] 20 Fixing part
[0540] 41 Adhesive layer
Claims
1. An optical thin film, which is a foldable optical thin film for an image display device, comprising: Polyester film as substrate, Functional layer disposed on the first side of the substrate Resin layer A disposed between the substrate and the functional layer, and A resin layer B disposed on the second side of the substrate, which is opposite to the first side. The thickness of resin layer A is greater than 10 nm and less than 500 nm. The thickness of the resin layer B is greater than 1 nm and less than 200 nm. When repeatedly folded 180° 10,000 times with the functional layer as the inside and the opposite edges of the optical film spaced 10 mm apart, no cracks or breaks occur in the optical film.
2. The optical film of claim 1, wherein, The refractive index of the resin layer A is lower than that of the substrate but higher than that of the functional layer.
3. The optical film of claim 1, wherein, Resin layer C is disposed between the substrate and resin layer A.
4. The optical film of claim 3, wherein, The thickness of the resin layer C is greater than 30 nm and less than 200 nm.
5. The optical thin film according to claim 1, wherein, An adhesive layer is also provided on the second side of the polyester film, which serves as the substrate and is located opposite to the first side. The adhesive layer has a film thickness of 25 μm or more and 300 μm or less. The shear storage modulus G' of the optical thin film in the frequency region above 500Hz and below 1000Hz at 25℃ exceeds 200MPa and is below 1200MPa. The shear loss modulus G” of the optical thin film in the frequency region of 25°C and above 500Hz and below 1000Hz is above 3MPa and below 150MPa.
6. The optical film of claim 5, wherein, The resin layer B is disposed between the substrate and the adhesive layer.
7. The optical film of claim 1, wherein, The yellow index of the optical film is below 15.
8. The optical film of claim 1, wherein, When repeatedly folded 180° with the functional layer on the outside and the opposite edges of the optical film spaced 30 mm apart, the optical film does not crack or break.
9. The optical thin film according to claim 1, wherein, Resin layer A is a cured layer of a curable resin composition formed from a composition comprising polycarbonate polyurethane resin (A-1), polyester resin (A-2), end-capped isocyanate crosslinking agent (A-3), and particles (A-4), wherein the polyester resin (A-2) has a fused polycyclic aromatic structure.
10. The optical thin film according to claim 1, wherein, Resin layer B is a cured layer of a curable resin composition formed from a composition comprising polycarbonate polyurethane resin (B-1), polyester resin (B-2), end-capped isocyanate crosslinking agent (B-3), and particles (B-4), wherein the polyester resin (B-2) has a fused polycyclic aromatic structure.
11. The optical thin film according to claim 3, wherein, Resin layer C is a cured layer of a curable resin composition formed from a composition comprising polycarbonate polyurethane resin (C-1), polyester resin (C-2), end-capped isocyanate crosslinking agent (C-3), and particles (C-4), wherein the polyester resin (C-2) has a fused polycyclic aromatic structure.
12. The optical thin film according to claim 9, 10 or 11, wherein, At least one of the polyester resins (A-2), (B-2), and (C-2) containing fused polycyclic aromatic structures in resin layers A, B, and C has a naphthalene skeleton in its molecule.
13. A method for manufacturing an optical thin film, which is the method for manufacturing an optical thin film according to claim 1, comprising: A functional layer is manufactured on the first side of the polyester film, which serves as the substrate, through a coating process.
14. A foldable image display device comprising a display element and an optical thin film of claim 1 disposed further toward the observer than the display element.
15. The image display device according to claim 14, wherein, The display element is an organic light-emitting diode (OLED) element.
Citation Information
Patent Citations
Window film for display device, and display device including the same
JP2016125063A
